Photomask blank, method for manufacturing photomask, and method for manufacturing display device

By adjusting the atomic ratio of transition metal to silicon and the sputtering gas pressure, a thin film for pattern formation with a columnar structure is formed, which solves the etching speed and cleaning resistance of the fine phase shift film pattern, and achieves efficient wet etching and high precision transfer effect.

CN119126477APending Publication Date: 2024-12-13HOYA CORPORATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411346726.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2019-11-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The prior art is difficult to form a fine phase shift film pattern with a pore diameter of less than 6 μm and a line width of less than 4 μm in the production of high-fine panels, and the cleaning resistance of the phase shift mask blank and the phase shift mask is insufficient, resulting in a wet etching speed. Slow and transparent substrate transmittance decreases.

Method used

By adjusting the atomic ratio of transition metal to silicon to 1:3 or more, and increasing the sputtering gas pressure to 0.7 Pa or more and 3.0 Pa or less in the film-forming chamber, a thin film for pattern formation with a columnar structure is formed, and the etching is shortened by wet etching Time and improve cleaning resistance.

Benefits of technology

It is possible to form a transfer pattern with good cross-sectional shape in a short time, avoid damage to the substrate by the wet etching liquid and reduce the transmittance of the transparent substrate, and improve the cleaning resistance and transfer accuracy of the pattern.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119126477A_ABST
    Figure CN119126477A_ABST
Patent Text Reader

Abstract

The present invention provides a photomask blank which can shorten the over-etching time and can form a transfer pattern having a good cross-sectional shape when forming the transfer pattern by wet etching a thin film for pattern formation. A photomask blank having a pattern-forming thin film on a transparent substrate, the photomask blank being an original plate for forming a photomask having a transfer pattern on the transparent substrate by wet etching the pattern-forming thin film, the pattern-forming thin film containing a transition metal and silicon, and the transfer pattern being formed on the transparent substrate by wet etching the pattern-forming thin film. The pattern-forming thin film has a columnar structure.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application filed on November 27, 2019, with application number 201911179769.3, and invention name “Photomask blank, method for manufacturing photomask, and method for manufacturing display device”. Technical Field

[0002] The present invention relates to a photomask blank, a method for manufacturing the photomask blank, a method for manufacturing a photomask, and a display device. Background Art

[0003] In recent years, for display devices such as FPD (Flat Panel Display) represented by LCD (Liquid Crystal Display), not only are large screens and wide viewing angles being rapidly developed, but also high-definition and high-speed display are being rapidly developed. In order to achieve this high-definition and high-speed display, one of the necessary elements is to manufacture electronic circuit patterns such as components and wiring that are fine and have high dimensional accuracy. The patterning of electronic circuits for the display device mostly uses photolithography. Therefore, it is necessary to form a photomask such as a phase shift mask and a binary mask for the manufacture of a display device with a fine and high-precision pattern.

[0004] For example, Patent Document 1 discloses a phase reversal mask blank having a phase reversal film on a transparent substrate. In the mask blank, the phase reversal film is composed of a multilayer film of two or more layers formed of a metal silicide compound containing at least one light element substance among oxygen (O), nitrogen (N), and carbon (C), and is made to have a reflectivity of 35% or less and a transmittance of 1% to 40% for exposure light of a composite wavelength containing i-line (365nm), h-line (405nm), and g-line (436nm), and a gradient of a pattern cross section is formed sharply when forming a pattern, and the metal silicide compound is formed by injecting a reactive gas containing the above light element substance and an inactive gas at a ratio of 0.5:9.5 to 4:6.

[0005] In addition, Patent Document 2 discloses a phase shift mask blank, which includes a transparent substrate, a light semi-transmissive film, and an etching mask film, wherein the light semi-transmissive film has the property of changing the phase of exposure light and is composed of a metal silicide material, and the etching mask film is composed of a chromium-based material. In the phase shift mask blank, a composition gradient region is formed at the interface between the light semi-transmissive film and the etching mask film. In the composition gradient region, the proportion of a component that slows down the wet etching speed of the light semi-transmissive film increases in the depth direction. Moreover, the oxygen content in the composition gradient region is less than 10 atomic %.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Korean Patent No. 1801101

[0009] Patent Document 2: Japanese Patent No. 6101646 Summary of the invention

[0010] Problems to be solved by the invention

[0011] In recent years, phase shift masks used in the production of high-definition (1000 ppi or more) panels have been required to have fine phase shift film patterns with an aperture of 6 μm or less and a line width of 4 μm or less in order to transfer high-resolution patterns. Specifically, phase shift masks with fine phase shift film patterns with an aperture of 1.5 μm are required.

[0012] In addition, in order to achieve higher resolution pattern transfer, a phase shift mask blank having a phase shift film with a transmittance of 15% or more to exposure light and a phase shift mask formed with a phase shift film pattern with a transmittance of 15% or more to exposure light are required. It should be noted that in terms of the cleaning resistance (chemical properties) of the phase shift mask blank and the phase shift mask, a phase shift mask blank and a phase shift mask in which optical property changes caused by film reduction and surface composition changes of the phase shift film and the phase shift film pattern are suppressed are required, the phase shift mask blank is formed with a phase shift film having cleaning resistance, and the phase shift mask is formed with a phase shift film pattern having cleaning resistance.

[0013] In order to meet the requirements for the transmittance of exposure light and the requirements for cleaning resistance, it is effective to increase the ratio of silicon in the atomic ratio of metal to silicon in the metal silicide compound (metal silicide-type material) constituting the phase shift film. However, there are problems such as a significant delay in the wet etching rate (long wet etching time), damage to the substrate by the wet etching solution, and a decrease in the transmittance of the transparent substrate.

[0014] Furthermore, in the case of a binary mask blank having a light-shielding film containing a transition metal and silicon, when a light-shielding pattern is formed on the light-shielding film by wet etching, there is also a demand for cleaning resistance, and the same problem as described above exists.

[0015] Therefore, the present invention is completed to solve the above-mentioned problems, and an object of the present invention is to provide a photomask blank, a method for manufacturing a photomask blank, a method for manufacturing a photomask, and a method for manufacturing a display device, which can shorten the wet etching time when a transfer pattern is formed by wet etching on a pattern-forming thin film such as a phase shift film or a light-shielding film containing a transition metal and silicon, thereby forming a transfer pattern with a good cross-sectional shape.

[0016] Solutions to the problem

[0017] The inventors have conducted in-depth research on countermeasures for solving these problems. First, a material in which the atomic ratio of transition metal to silicon in the pattern-forming film is transition metal: silicon = 1:3 or more is made. In order to shorten the time of wet etching of the pattern-forming film using a wet etching solution, the oxygen contained in the sputtering gas introduced into the film forming chamber is adjusted so that the pattern-forming film contains a large amount of oxygen (O), thereby forming a pattern-forming film. As a result, although the wet etching speed for forming the transfer pattern becomes faster, the refractive index of the phase shift film in the phase shift mask blank to the exposure light is reduced, so the film thickness required to obtain the desired phase difference (for example, 180°) is thickened. In addition, for the light-shielding film in the binary mask blank, in order to reduce the extinction coefficient to the exposure light, the film thickness required to obtain the desired light-shielding performance (for example, the optical density (OD) is 3 or more) is thickened. The thickening of the film thickness of the pattern-forming film is not conducive to pattern formation by wet etching, and due to the thickening of the film thickness, the effect of shortening the wet etching time is limited. On the other hand, when the atomic ratio of transition metal to silicon is set to the above-mentioned transition metal: silicon = 1:3 or more, there are advantages such as improving the cleaning resistance of the pattern-forming film. Therefore, from this point of view, it is not preferred to deviate from the above-mentioned composition ratio of transition metal to silicon.

[0018] Therefore, the inventors changed their minds and studied the adjustment of the pressure of the sputtering gas in the film forming chamber to change the film structure. When a film is formed on a substrate to form a pattern-forming thin film, the sputtering gas pressure in the film forming chamber is usually set to 0.1 to 0.5 Pa. However, the inventors intentionally set the sputtering gas pressure to be greater than 0.5 Pa to form a pattern-forming thin film. Then, the pattern-forming thin film was formed with a sputtering pressure of more than 0.7 Pa and less than 3.0 Pa, preferably with a sputtering gas pressure of more than 0.8 Pa and less than 3.0 Pa. It was found that it not only has suitable properties as a thin film, but also can greatly shorten the etching time when a transfer pattern is formed on the pattern-forming thin film by wet etching, thereby forming a transfer pattern with a good cross-sectional shape. Moreover, the pattern-forming thin film formed in this way has a columnar structure that is not found in a conventional pattern-forming thin film. The present invention is the result of the above in-depth research and has the following structure.

[0019] (Scheme 1) A photomask blank having a pattern-forming thin film on a transparent substrate, wherein:

[0020] The photomask blank is an original plate for forming a photomask, and the photomask is a photomask having a transfer pattern on the transparent substrate obtained by wet etching the pattern-forming thin film.

[0021] The pattern-forming thin film contains a transition metal and silicon.

[0022] The pattern-forming thin film has a columnar structure.

[0023] (Scheme 2) A photomask blank according to scheme 1, wherein in the spatial spectrum distribution of the pattern forming film, there is a spatial spectrum having a signal intensity of 1.0% or more relative to the maximum signal intensity corresponding to the origin of the spatial frequency,

[0024] The spatial spectrum distribution is obtained as follows: for an image obtained by observing the cross section of the photomask blank with a scanning electron microscope at a magnification of 80,000 times, image data of 64 pixels in length by 256 pixels in width are extracted from an area including the center portion in the thickness direction of the pattern-forming film, and the image data is Fourier transformed.

[0025] (Scheme 3) A photomask blank according to scheme 2, wherein, in the pattern-forming film, when the maximum spatial frequency is set to 100%, the signal having a signal intensity of 1.0% or more is located at a spatial frequency that is 2.0% or more away from the origin of the spatial frequency.

[0026] (Scheme 4) The photomask blank according to any one of schemes 1 to 3, wherein the atomic ratio of the transition metal and the silicon contained in the pattern-forming thin film is transition metal:silicon=1:3 or more and 1:15 or less.

[0027] (Structure 5) The photomask blank according to any one of Structures 1 to 4, wherein the pattern-forming thin film contains at least nitrogen or oxygen.

[0028] (Scheme 6) A photomask blank according to scheme 5, wherein the pattern-forming thin film contains nitrogen, and the atomic ratio of the transition metal to the silicon contained in the pattern-forming thin film is transition metal:silicon=1:3 or more and 1:15 or less,

[0029] The pattern-forming film has an indentation hardness of 18 GPa or more and 23 GPa or less as determined by a nanoindentation method.

[0030] (Structure 7) The photomask blank according to Structure 6, wherein the nitrogen content is 35 atomic % or more and 60 atomic % or less.

[0031] (Scheme 8) The photomask blank according to any one of schemes 1 to 7, wherein the transition metal is molybdenum.

[0032] (Scheme 9) A photomask blank according to any one of schemes 1 to 8, wherein the pattern-forming film is a phase shift film having the following optical properties: a transmittance of a representative wavelength of exposure light of greater than 1% and less than 80%, and a phase difference of greater than 160° and less than 200°.

[0033] (Structure 10) The photomask blank according to any one of Structures 1 to 9, comprising an etching mask film having a different etching selectivity with respect to the pattern-forming thin film on the pattern-forming thin film.

[0034] (Scheme 11) The photomask blank according to scheme 10, wherein the etching mask film is formed of a material containing chromium but substantially containing no silicon.

[0035] (Scheme 12) A method for manufacturing a photomask blank, which is a method for manufacturing a photomask blank in which a pattern-forming thin film containing a transition metal and silicon is formed on a transparent substrate by a sputtering method, the method comprising:

[0036] The pattern-forming thin film is formed in a film forming chamber using a transition metal silicide target containing a transition metal and silicon, and a sputtering gas pressure in the film forming chamber to which a sputtering gas is supplied is 0.7 Pa or more and 3.0 Pa or less.

[0037] (Scheme 13) A method for manufacturing a photomask blank according to scheme 12, wherein the atomic ratio of the transition metal to silicon in the transition metal silicide target is transition metal:silicon=1:3 or more and 1:15 or less.

[0038] (Scheme 14) A method for manufacturing a photomask blank according to scheme 12 or 13, wherein an etching mask film is formed on the pattern-forming thin film using a sputtering target, and the sputtering target is formed of a material having a different etching selectivity to the pattern-forming thin film.

[0039] (Scheme 15) The method for manufacturing a photomask blank according to scheme 14, wherein the pattern forming thin film and the etching mask film are formed using an inline sputtering device.

[0040] (Scheme 16) A method for manufacturing a photomask, the method comprising:

[0041] A step of preparing the photomask blank according to any one of claims 1 to 9, or a photomask blank manufactured by the method for manufacturing a photomask blank according to claim 12 or 13; and

[0042] A step of forming a resist film on the pattern-forming thin film, and wet-etching the pattern-forming thin film using a resist film pattern formed by the resist film as a mask to form a transfer pattern on the transparent substrate.

[0043] (Scheme 17) A method for manufacturing a photomask, the method comprising:

[0044] A step of preparing the photomask blank described in claim 10 or 11, or a photomask blank manufactured by the method for manufacturing a photomask blank described in claim 14 or 15;

[0045] forming a resist film on the etching mask film, and wet-etching the etching mask film using the resist film pattern formed by the resist film as a mask to form an etching mask film pattern on the pattern-forming thin film; and

[0046] A step of wet-etching the pattern-forming thin film using the etching mask film pattern as a mask to form a transfer pattern on the transparent substrate.

[0047] (Scheme 18) A method for manufacturing a display device, the method comprising:

[0048] An exposure step of placing the photomask obtained by the photomask manufacturing method described in claim 16 or 17 on a mask stage of an exposure device, and transferring the transfer pattern formed on the photomask to a resist formed on a display device substrate by exposure.

[0049] In addition, the inventor has studied the change of film structure by adjusting the pressure of the sputtering gas in the film forming chamber, and found the following other schemes. As mentioned above, the inventor intentionally sets the sputtering gas pressure to be greater than 0.5Pa, and forms a film for pattern formation. And it is found that the result of forming a film for pattern formation with a sputtering gas pressure of more than 0.7Pa is that the etching time can be greatly shortened, a transfer pattern with a good cross-sectional shape can be formed, and the surface roughness of the transparent substrate can be suppressed. On the other hand, it is known that when the sputtering gas pressure during film formation is set too large, the pattern formation film cannot obtain enough washing resistance. The result of the inventor's in-depth study found that by forming a film for pattern formation with a sputtering gas pressure of more than 0.7Pa and less than 2.4Pa, it not only has the suitable characteristics as a pattern formation film, but also can form a transfer pattern with a good cross-sectional shape, the surface roughness of the transparent substrate can be suppressed, and the washing resistance of the pattern formation film can be improved.

[0050] Then, the inventor further explored the physical index of the pattern-forming film with such excellent characteristics. It was found that the indentation hardness of the pattern-forming film was related to the wet etching rate. This point was studied in depth, and it was found that when the indentation hardness obtained by the nanoindentation method was more than 18GPa and less than 23GPa, it not only had the suitable characteristics as the pattern-forming film, but also when the transfer pattern was formed on the pattern-forming film by wet etching, a transfer pattern with a good cross-sectional shape could be formed, the surface roughness of the transparent substrate could be suppressed, and the cleaning resistance of the pattern-forming film could be improved.

[0051] (Other solution 1) A photomask blank having a pattern-forming thin film on a transparent substrate, wherein:

[0052] The photomask blank is a master plate for forming a photomask having a transfer pattern on the transparent substrate by wet etching the pattern-forming thin film.

[0053] The pattern-forming thin film contains a transition metal, silicon, and nitrogen, and the atomic ratio of the transition metal to the silicon contained in the pattern-forming thin film is transition metal:silicon=1:3 or more and 1:15 or less,

[0054] The pattern-forming film has an indentation hardness of 18 GPa or more and 23 GPa or less as measured by a nanoindentation method.

[0055] (Other Aspect 2) The photomask blank according to Other Aspect 1, wherein the transition metal is molybdenum.

[0056] (Other Aspect 3) The photomask blank according to Other Aspect 1 or 2, wherein the nitrogen content is 35 atomic % or more and 60 atomic % or less.

[0057] (Other Scheme 4) A photomask blank according to any one of Other Schemes 1 to 3, wherein the pattern-forming film is a phase shift film having the following optical properties: a transmittance of a representative wavelength of exposure light of greater than 1% and less than 80%, and a phase difference of greater than 160° and less than 200°.

[0058] (Other Aspect 5) The photomask blank according to any one of Other Aspects 1 to 4, further comprising an etching mask film having a different etching selectivity with respect to the pattern-forming thin film on the pattern-forming thin film.

[0059] (Other solution 6) The photomask blank according to other solution 5, wherein the etching mask film is formed of a material containing chromium but substantially containing no silicon.

[0060] (Other solution 7) A method for manufacturing a photomask, the method comprising:

[0061] A step of preparing a photomask blank according to any one of other aspects 1 to 4; and

[0062] A step of forming a resist film on the pattern-forming thin film, and wet-etching the pattern-forming thin film using a resist film pattern formed by the resist film as a mask to form a transfer pattern on the transparent substrate.

[0063] (Other solution 8) A method for manufacturing a photomask, the method comprising:

[0064] A step of preparing a photomask blank as described in other embodiments 5 or 6;

[0065] forming a resist film on the etching mask film, and wet-etching the etching mask film using the resist film pattern formed by the resist film as a mask to form an etching mask film pattern on the pattern-forming thin film; and

[0066] A step of wet-etching the pattern-forming thin film using the etching mask film pattern as a mask to form a transfer pattern on the transparent substrate.

[0067] (Other solution 9) A method for manufacturing a display device, the method comprising:

[0068] An exposure step of placing the photomask obtained by the photomask manufacturing method described in other aspect 7 or 8 on a mask stage of an exposure device, and transferring the transfer pattern formed on the photomask to a resist formed on a display device substrate by exposure.

[0069] Effects of the Invention

[0070] According to the photomask blank or the method for manufacturing the photomask blank of the present invention, when a desired fine transfer pattern is formed by wet etching a transfer pattern film, from the viewpoint of cleaning resistance, etc., when the pattern forming film is made of a metal silicide compound rich in silicon, a photomask blank can be obtained that can form a transfer pattern with a good cross-sectional shape in a short etching time and does not cause a decrease in the transmittance of a transparent substrate due to damage to the substrate by a wet etching solution. In addition, according to the photomask blank of another embodiment of the present invention, when a desired fine transfer pattern is formed by wet etching a transfer pattern film, a photomask blank can be obtained that can form a transfer pattern with a good cross-sectional shape, can suppress the surface roughness of the transparent substrate, and can improve the cleaning resistance of the transfer pattern film.

[0071] In addition, according to the method for manufacturing a photomask of the present invention, a photomask is manufactured using the above-mentioned photomask blank. Therefore, from the viewpoint of cleaning resistance, when the film for pattern formation is made of a metal silicide compound rich in silicon, a photomask having a transfer pattern with good transfer accuracy and without a reduction in the transmittance of a transparent substrate caused by damage to the substrate by a wet etching solution can be manufactured. This photomask can cope with the miniaturization of line and space patterns and contact holes. In addition, according to the method for manufacturing a photomask of other schemes of the present invention, a photomask can be manufactured that can form a transfer pattern with a good cross-sectional shape, can suppress the surface roughness of a transparent substrate, and can improve the cleaning resistance of the film for the transfer pattern.

[0072] In addition, according to the method for manufacturing a display device of the present invention, a display device is manufactured using a photomask manufactured using the above-mentioned photomask blank or obtained by the above-mentioned method for manufacturing a photomask, so that a display device having a fine line and space pattern and contact holes can be manufactured. BRIEF DESCRIPTION OF THE DRAWINGS

[0073] Figure 1 This is an explanatory diagram showing the film structure of the phase shift mask blank according to the first embodiment.

[0074] Figure 2 It is an explanatory diagram showing the film structure of the phase shift mask blank according to the second embodiment.

[0075] Figure 3 (a) to (e) are explanatory diagrams showing the manufacturing process of the phase shift mask according to the third embodiment.

[0076] Figure 4 (a) to (c) are explanatory diagrams showing the manufacturing process of the phase shift mask according to the fourth embodiment.

[0077] Figure 5 (a) is an enlarged photograph (image data) of the center portion in the thickness direction of the phase shift film in the cross-sectional SEM image of the phase shift mask blank of Example 1. Figure 5 (b) is the result of Fourier transforming the enlarged photograph (image data) of (a).

[0078] Figure 6 This is a dark-field top-view STEM photograph of the phase shift film in the phase shift mask blank of Example 1.

[0079] Figure 7 This is a cross-sectional photograph of the phase shift mask of Example 1.

[0080] Figure 8 (a) is an enlarged photograph (image data) of the center portion in the thickness direction of the phase shift film in the cross-sectional SEM image of the phase shift mask blank of Example 2. Figure 8 (b) in the above formula is Figure 8 The enlarged photograph (image data) of (a) is Fourier transformed.

[0081] Fig. 9 This is a cross-sectional photograph of the phase shift mask of Example 2.

[0082] Fig.10 (a) is an enlarged photograph (image data) of the center portion in the thickness direction of the phase shift film in the cross-sectional SEM image of the phase shift mask blank of Example 3. Fig.10 (b) in the above formula is Fig.10 The enlarged photograph (image data) of (a) is Fourier transformed.

[0083] Fig.11 This is a cross-sectional photograph of the phase shift mask of Example 3.

[0084] Fig.12 (a) is an enlarged photograph (image data) of the center portion in the thickness direction of the phase shift film in the cross-sectional SEM image of the phase shift mask blank of Comparative Example 1. Fig.12 (b) in the above formula is Fig.12 The enlarged photograph (image data) of (a) is Fourier transformed.

[0085] Fig.13 This is a cross-sectional photograph of the phase shift mask of Comparative Example 1.

[0086] Fig.14 This is a graph showing the relationship among the etching rate of the phase shift film of the phase shift mask of other Examples 1 to 4 and other Comparative Examples 1 and 2, the sputtering gas pressure, and the indentation hardness.

[0087] Explanation of symbols

[0088] 10…Phase shift mask blanks

[0089] 20…Transparent substrate

[0090] 30…Phase shift film

[0091] 30a…Phase shift film pattern

[0092] 40…Etching mask film

[0093] 40a ... first etching mask film pattern

[0094] 40b ... second etching mask film pattern

[0095] 50…1st resist film pattern

[0096] 60…Second resist pattern

[0097] 100…Phase shift mask DETAILED DESCRIPTION

[0098] Implementation method 1.2.

[0099] In Embodiments 1 and 2, a phase shift mask blank is described. The phase shift mask blank of Embodiment 1 is a master for forming a phase shift mask having a phase shift film pattern on a transparent substrate by wet etching the phase shift film using an etching mask film pattern having a desired pattern formed on an etching mask film as a mask. In addition, the phase shift mask blank of Embodiment 2 is a master for forming a phase shift film having a phase shift film pattern on a transparent substrate by wet etching the phase shift film using an etching resist film pattern having a desired pattern formed on a resist film as a mask.

[0100] Figure 1 1 is an explanatory diagram showing a film structure of the phase shift mask blank 10 according to the first embodiment.

[0101] Figure 1 The phase shift mask blank 10 shown includes a transparent substrate 20 , a phase shift film 30 formed on the transparent substrate 20 , and an etching mask film 40 formed on the phase shift film 30 .

[0102] Figure 2 It is an explanatory diagram showing the film structure of the phase shift mask blank 10 according to the second embodiment.

[0103] Figure 2 The phase shift mask blank 10 shown includes a transparent substrate 20 and a phase shift film 30 formed on the transparent substrate 20 .

[0104] Hereinafter, the transparent substrate 20 , the phase shift film 30 , and the etching mask film 40 constituting the phase shift mask blank 10 according to the first and second embodiments will be described.

[0105] The transparent substrate 20 is transparent to the exposure light. When there is no surface reflection loss, the transparent substrate 20 has a transmittance of 85% or more, preferably a transmittance of 90% or more, to the exposure light. The transparent substrate 20 is made of a material containing silicon and oxygen, and can be composed of glass materials such as synthetic quartz glass, quartz glass, aluminosilicate glass, soda-lime glass, and low thermal expansion glass (SiO2-TiO2 glass, etc.). In the case where the transparent substrate 20 is composed of low thermal expansion glass, the position change of the phase shift film pattern caused by the thermal deformation of the transparent substrate 20 can be suppressed. In addition, the transparent substrate 20 used in the display device application is usually a rectangular substrate, and a substrate with a short side length of 300 mm or more can be used. The present invention is a phase shift mask blank, which can provide a phase shift mask, which can stably transfer a fine phase shift film pattern, for example, less than 2.0 μm, formed on a transparent substrate even if the short side length of the transparent substrate is large and is 300 mm or more.

[0106] The phase shift film 30 is made of a transition metal silicide material containing a transition metal and silicon. As the transition metal, molybdenum (Mo), tantalum (Ta), tungsten (W), titanium (Ti), zirconium (Zr), etc. are suitable, and molybdenum (Mo) is particularly preferred.

[0107] In addition, the phase shift film 30 preferably contains at least nitrogen or oxygen. In the above-mentioned transition metal silicide-based materials, oxygen as a light element component has an effect of reducing the extinction coefficient compared with nitrogen as a light element component, and can reduce the content of other light element components (nitrogen, etc.) for obtaining the desired transmittance, and can effectively reduce the reflectivity of the surface and back of the phase shift film 30. In addition, in the above-mentioned transition metal silicide-based materials, nitrogen as a light element component has an effect of not reducing the refractive index compared with oxygen as a light element component, so the film thickness for obtaining the desired phase difference can be reduced. In addition, the total content of light element components including oxygen and nitrogen contained in the phase shift film 30 is preferably 40 atomic % or more, more preferably 40 atomic % or more and 70 atomic % or less, and preferably 50 atomic % or more and 65 atomic % or less. In addition, when oxygen is contained in the phase shift film 30, it is preferable that the content of oxygen is greater than 0 atomic % and less than 40 atomic % from the perspective of defect quality and chemical resistance.

[0108] As transition metal silicide materials, for example, nitrides of transition metal silicides, oxides of transition metal silicides, oxynitrides of transition metal silicides, and carbonitride oxides of transition metal silicides can be cited. In addition, from the viewpoint of being easy to obtain an excellent pattern cross-sectional shape by wet etching, the transition metal silicide materials are preferably molybdenum silicide materials (MoSi materials), zirconium silicide materials (ZrSi materials), and molybdenum zirconium silicide materials (MoZrSi materials), and particularly preferably molybdenum silicide materials (MoSi materials).

[0109] Furthermore, in order to reduce film stress and control the wet etching rate, the phase shift film 30 may contain other light element components such as carbon and helium in addition to the above-mentioned oxygen and nitrogen.

[0110] The phase shift film 30 has a function of adjusting the reflectance of light incident from the transparent substrate 20 side (hereinafter, sometimes referred to as back surface reflectance) and a function of adjusting the transmittance and phase difference of exposure light.

[0111] The phase shift film 30 can be formed by a sputtering method.

[0112] The phase shift film 30 preferably has a columnar structure. The columnar structure can be confirmed by observing the phase shift film 30 through a cross-sectional SEM. That is, the columnar structure of the present invention refers to a state in which the particles of the transition metal silicide compound containing transition metal and silicon constituting the phase shift film 30 have a columnar particle structure extending in the film thickness direction of the phase shift film 30 (the direction in which the above-mentioned particles are accumulated). It should be noted that in the present application, particles whose length in the film thickness direction is longer than their length in the perpendicular direction are referred to as columnar particles. That is, the phase shift film 30 forms columnar particles extending in the film thickness direction within the entire surface of the transparent substrate 20. In addition, in the phase shift film 30, by adjusting the film forming conditions (sputtering pressure, etc.), a sparse portion (hereinafter sometimes referred to as a "sparse portion") having a relatively low density compared to the columnar particles is formed. It should be noted that, for the phase shift film 30, in order to effectively suppress side etching during wet etching and make the pattern cross-sectional shape better, as a preferred form of the columnar structure of the phase shift film 30, columnar particles extending in the film thickness direction are preferably formed irregularly in the film thickness direction. It is further preferred that the columnar particles of the phase shift film 30 are in a state where the lengths in the film thickness direction are not aligned. Moreover, it is preferred that the sparse portion of the phase shift film 30 is formed continuously in the film thickness direction. In addition, it is preferred that the sparse portion of the phase shift film 30 is formed intermittently in a direction perpendicular to the film thickness direction. As a preferred form of the columnar structure of the phase shift film 30, the index obtained by Fourier transforming the image obtained by the above-mentioned cross-sectional SEM observation is expressed as follows. That is, the columnar structure of the phase shift film 30 is preferably in the following state: for an image obtained by observing the cross section of the phase shift mask blank by cross-sectional SEM at a magnification of 80,000 times, image data of 64 pixels in length and 256 pixels in width is extracted from the region including the central part in the thickness direction of the phase shift film 30, and the spatial spectrum obtained by Fourier transforming the image data has a signal intensity of 1.0% or more relative to the maximum signal intensity corresponding to the origin of the spatial frequency. By forming the phase shift film 30 into the columnar structure as described above, when wet etching is performed using a wet etching liquid, the wet etching liquid easily penetrates in the film thickness direction of the phase shift film 30, so that the wet etching speed can be increased and the wet etching time can be greatly shortened. Therefore, even if the phase shift film 30 is a metal silicide compound rich in silicon, the transmittance of the transparent substrate is not reduced due to damage to the substrate by the wet etching liquid. In addition, since the phase shift film 30 has a columnar structure extending in the film thickness direction, side etching during wet etching can be suppressed, and the cross-sectional shape of the pattern can be improved.

[0113] In addition, in the phase shift film 30, when the maximum spatial frequency is set to 100%, it is preferred that a signal having a signal strength of 1.0% or more relative to the maximum signal strength of the spatial spectrum distribution obtained by Fourier transform is located at a spatial frequency that is 2.0% or more away from the origin of the spatial frequency. A signal having a signal strength of 1.0% or more relative to the maximum signal strength is 2.0% or more away from the spatial frequency, indicating that a certain high spatial frequency component is included. That is, it indicates that the phase shift film 30 is a fine columnar structure, and the farther the spatial frequency is from the origin, the smaller the line edge roughness of the phase shift film pattern 30a formed by wet etching the phase shift film 30 is, and therefore it is preferred.

[0114] The indentation hardness of the phase shift film 30 is preferably 18 GPa or more and 23 GPa or less. The indentation hardness is a hardness measured using the principle of the nanoindentation method established in accordance with ISO14577.

[0115] By setting the indentation hardness of the phase shift film 30 to be greater than or equal to 18 GPa and less than or equal to 23 GPa, when wet etching is performed using a wet etching liquid, the wet etching liquid easily penetrates in the film thickness direction of the phase shift film 30, thereby increasing the wet etching speed and shortening the wet etching time. In addition, a phase shift film pattern 30a having not only suitable characteristics as the phase shift film 30 but also a good cross-sectional shape can be formed, the surface roughness of the transparent substrate 20 can be suppressed, and the cleaning resistance of the phase shift film 30 can be improved.

[0116] The atomic ratio of transition metal to silicon contained in the phase shift film 30 is preferably transition metal: silicon = 1:3 or more and 1:15 or less. In this range, the effect of suppressing the wet etching rate reduction of the phase shift film 30 during pattern formation by the columnar structure can be increased. In addition, the cleaning resistance of the phase shift film 30 can be improved, and the transmittance can be easily improved. In addition, in this range, the effect of suppressing the wet etching rate reduction of the phase shift film 30 during pattern formation can be increased by setting the indentation hardness to 18 GPa or more and 23 GPa or less. From the viewpoint of improving the cleaning resistance of the phase shift film 30, the atomic ratio of transition metal to silicon contained in the phase shift film 30 is preferably transition metal: silicon = 1:4 or more and 1:15 or less, and more preferably transition metal: silicon = 1:5 or more and 1:15 or less.

[0117] The transmittance of the phase shift film 30 with respect to the exposure light satisfies the value required as the phase shift film 30. The transmittance of the phase shift film 30 with respect to the light of a given wavelength (hereinafter referred to as a representative wavelength) included in the exposure light is preferably 1% or more and 80% or less, more preferably 15% or more and 65% or less, and further preferably 20% or more and 60% or less. That is, when the exposure light is a composite light including light of a wavelength range of 313nm or more and 436nm or less, the phase shift film 30 has the above transmittance with respect to the light of the representative wavelength included in the wavelength range. For example, when the exposure light is a composite light including i-line, h-line, and g-line, the phase shift film 30 has the above transmittance with respect to any one of the i-line, h-line, and g-line.

[0118] The transmittance can be measured using a phase shift measurement device or the like.

[0119] The phase difference of the phase shift film 30 with respect to the exposure light satisfies the value required as the phase shift film 30. The phase difference of the phase shift film 30 with respect to the light of the representative wavelength included in the exposure light is preferably 160° or more and 200° or less, and more preferably 170° or more and 190° or less. By utilizing this property, the phase of the light of the representative wavelength included in the exposure light can be changed to 160° or more and 200° or less. Therefore, a phase difference of 160° or more and 200° or less is generated between the light of the representative wavelength that has passed through the phase shift film 30 and the light of the representative wavelength that has only passed through the transparent substrate 20. That is, when the exposure light is a composite light including light of a wavelength range of 313nm or more and 436nm or less, the phase shift film 30 has the above-mentioned phase difference with respect to the light of the representative wavelength included in the wavelength range. For example, when the exposure light is a composite light including i-line, h-line and g-line, the phase shift film 30 has the above-mentioned phase difference with respect to any one of the i-line, h-line and g-line.

[0120] The phase difference can be measured using a phase shift measurement device or the like.

[0121] The back reflectivity of the phase shift film 30 is 15% or less, preferably 10% or less, in the wavelength range of 365nm to 436nm. In addition, when the exposure light includes a j line, the back reflectivity of the phase shift film 30 is preferably 20% or less, more preferably 17% or less, and further preferably 15% or less with respect to the light in the wavelength range of 313nm to 436nm. In addition, the back reflectivity of the phase shift film 30 is 0.2% or more in the wavelength range of 365nm to 436nm, preferably 0.2% or more with respect to the light in the wavelength range of 313nm to 436nm.

[0122] The back surface reflectance can be measured using a spectrophotometer or the like.

[0123] The phase shift film 30 may be composed of multiple layers or a single layer. A phase shift film 30 composed of a single layer is less likely to form an interface in the phase shift film 30, and is preferred from the viewpoint of easy control of the cross-sectional shape. On the other hand, a phase shift film 30 composed of multiple layers is preferred from the viewpoint of ease of film formation.

[0124] The etching mask film 40 is arranged on the upper side of the phase shift film 30, and is formed of a material having etching resistance to the etching solution for etching the phase shift film 30 (different from the etching selectivity of the phase shift film 30). In addition, the etching mask film 40 can have a function of blocking the exposure light from being transmitted, and can also have a function of reducing the film surface reflectivity, so that the film surface reflectivity of the phase shift film 30 is 15% or less relative to the light incident from the side of the phase shift film 30 in the wavelength range of 350nm to 436nm. The etching mask film 40 is composed of a chromium-based material containing chromium (Cr). As the chromium-based material, more specifically, chromium (Cr), or a material containing chromium (Cr) and at least one of oxygen (O), nitrogen (N), and carbon (C) can be cited. Alternatively, a material containing chromium (Cr) and at least one of oxygen (O), nitrogen (N), and carbon (C) and also containing fluorine (F) can be cited. For example, as a material constituting the etching mask film 40 , there can be cited Cr, CrO, CrN, CrF, CrCO, CrCN, CrON, CrCON, and CrCONF.

[0125] The etching mask film 40 can be formed by a sputtering method.

[0126] When the etching mask film 40 has a function of shielding exposure light from passing therethrough, the optical density of the exposure light in the portion where the phase shift film 30 and the etching mask film 40 are stacked is preferably 3 or more, more preferably 3.5 or more, and even more preferably 4 or more.

[0127] Optical density can be measured using a spectrophotometer or an OD meter.

[0128] Depending on the function, the etching mask film 40 may be formed of a single film having a uniform composition, may be formed of a plurality of films having different compositions, or may be formed of a single film having a composition that continuously changes in the thickness direction.

[0129] It should be noted that Figure 1 The phase shift mask blank 10 shown includes the etching mask film 40 on the phase shift film 30 , but the present invention can also be applied to a phase shift mask blank including the etching mask film 40 on the phase shift film 30 and an etching resist film on the etching mask film 40 .

[0130] Next, a method for manufacturing the phase shift mask blank 10 according to the first and second embodiments will be described. Figure 1 The phase shift mask blank 10 shown can be manufactured by performing the following phase shift film forming step and etching mask film forming step. Figure 2 The phase shift mask blank 10 shown can be manufactured through a phase shift film forming process.

[0131] Hereinafter, each step will be described in detail.

[0132] 1. Phase shift film formation process

[0133] First, prepare the transparent substrate 20. The transparent substrate 20 may be made of any glass material such as synthetic quartz glass, quartz glass, aluminosilicate glass, soda-lime glass, or low thermal expansion glass (SiO2-TiO2 glass, etc.) as long as it is transparent to exposure light.

[0134] Next, the phase shift film 30 is formed on the transparent substrate 20 by sputtering.

[0135] A transition metal silicide target containing a transition metal and silicon as the main component of the material constituting the phase shift film 30, or a transition metal silicide target containing a transition metal, silicon, oxygen and / or nitrogen is used as a sputtering target, and the phase shift film 30 is formed in a sputtering gas atmosphere, for example, a sputtering gas atmosphere formed by at least one inert gas selected from helium, neon, argon, krypton and xenon, or a sputtering gas atmosphere formed by a mixed gas of the above inert gas and an active gas selected from oxygen, nitrogen, carbon dioxide, nitric oxide and nitrogen dioxide and containing at least oxygen and nitrogen. Then, the phase shift film 30 is formed when the gas pressure in the film forming chamber during sputtering is 0.7 Pa or more and 3.0 Pa or less. It is preferred that the phase shift film 30 is formed when the gas pressure in the film forming chamber during sputtering is 0.8 Pa or more and 3.0 Pa or less. By setting the range of the gas pressure in this way, a columnar structure can be formed in the phase shift film 30. The columnar structure can not only suppress the side etching during the pattern formation described later, but also achieve a high etching rate. Here, from the viewpoints that the columnar structure has a large effect of suppressing the reduction of the wet etching rate, can improve the cleaning resistance of the phase shift film 30, and can easily improve the transmittance, the atomic ratio of transition metal to silicon in the transition metal silicide target is preferably transition metal:silicon = 1:3 or more and 1:15 or less.

[0136] The composition and thickness of the phase shift film 30 can be adjusted so that the phase shift film 30 has the above-mentioned phase difference and transmittance. The composition of the phase shift film 30 can be controlled by the content ratio of the elements constituting the sputtering target (for example, the ratio of the content ratio of transition metals to the content ratio of silicon), the composition and flow rate of the sputtering gas, etc. The thickness of the phase shift film 30 can be controlled by the sputtering power, the sputtering time, etc. In addition, the phase shift film 30 is preferably formed using an inline sputtering device. In the case where the sputtering device is an inline sputtering device, the thickness of the phase shift film 30 can be controlled by the conveying speed of the substrate. Thus, the content ratio of the light element components including oxygen and nitrogen in the phase shift film 30 can be controlled to be greater than 40 atomic % and less than 70 atomic %.

[0137] When the phase shift film 30 is formed of a single film, the composition and flow rate of the sputtering gas are appropriately adjusted, and the above-mentioned film forming process is performed only once. When the phase shift film 30 is formed of a plurality of films having different compositions, the composition and flow rate of the sputtering gas are appropriately adjusted, and the above-mentioned film forming process is performed multiple times. The phase shift film 30 can be formed using a target material having different content ratios of elements constituting the sputtering target material. When multiple film forming processes are performed, the sputtering power applied to the sputtering target material can be changed according to the film forming process.

[0138] 2. Surface treatment process

[0139] In the case where the phase shift film 30 is formed of a transition metal silicide material containing oxygen, such as a transition metal silicide oxide containing a transition metal, silicon, and oxygen, or a transition metal silicide oxynitride containing a transition metal, silicon, oxygen, and nitrogen, a surface treatment step for adjusting the surface oxidation state of the phase shift film 30 may be performed on the surface of the phase shift film 30 in order to suppress the infiltration of an etching solution due to the presence of the transition metal oxide. It should be noted that, in the case where the phase shift film 30 is formed of a transition metal silicide nitride containing a transition metal, silicon, and nitrogen, the content of the transition metal oxide is less than that of the above-mentioned transition metal silicide material containing oxygen. Therefore, in the case where the material of the phase shift film 30 is a transition metal silicide nitride, the above-mentioned surface treatment step may be performed or may not be performed.

[0140] Examples of the surface treatment process for adjusting the surface oxidation state of the phase shift film 30 include a method of surface treatment using an acidic aqueous solution, a method of surface treatment using an alkaline aqueous solution, and a method of surface treatment by dry treatment such as ashing.

[0141] Thus, the phase shift mask blank 10 of Embodiment 2 can be obtained. In the production of the phase shift mask blank 10 of Embodiment 1, the following etching mask film forming step can be further performed.

[0142] 3. Etching mask film formation process

[0143] After the phase shift film forming step, a surface treatment for adjusting the surface oxidation state of the phase shift film 30 may be performed as needed, and then an etching mask film 40 is formed on the phase shift film 30 by sputtering. The etching mask film 40 is preferably formed using an inline sputtering device. When the sputtering device is an inline sputtering device, the thickness of the etching mask film 40 can be controlled by the conveying speed of the transparent substrate 20.

[0144] Using a sputtering target containing chromium or a chromium compound (chromium oxide, chromium nitride, chromium carbide, chromium oxynitride, chromium carbonitride, etc.), the etching mask film 40 is formed in the following sputtering gas atmosphere, the sputtering gas atmosphere is, for example, a sputtering gas atmosphere formed by at least one inactive gas selected from helium, neon, argon, krypton and xenon, or a sputtering gas atmosphere formed by a mixed gas of an inactive gas and an active gas, the inactive gas includes at least one selected from helium, neon, argon, krypton and xenon, and the active gas includes at least one selected from oxygen, nitrogen, nitric oxide gas, nitrogen dioxide gas, carbon dioxide gas, hydrocarbon gas, fluorine gas. As hydrocarbon gas, for example: methane gas, butane gas, propane gas, styrene gas, etc. can be cited. Then, by adjusting the gas pressure in the film forming chamber during sputtering, the etching mask film 40 can be formed into a columnar structure in the same manner as the phase shift film 30. Thus, not only can the side etching during the pattern formation described later be suppressed, but also a high etching rate can be achieved.

[0145] In the case where the etching mask film 40 is formed of a single film having a uniform composition, the above-mentioned film forming process is performed only once without changing the composition and flow rate of the sputtering gas. In the case where the etching mask film 40 is formed of a plurality of films having different compositions, the above-mentioned film forming process is performed a plurality of times while changing the composition and flow rate of the sputtering gas according to the film forming process. In the case where the etching mask film 40 is formed of a single film having a composition that continuously changes along the thickness direction, the composition and flow rate of the sputtering gas are changed together with the elapsed time of the film forming process, and the above-mentioned film forming process is performed only once.

[0146] In this way, the phase shift mask blank 10 of the first embodiment can be obtained.

[0147] It should be noted that due to Figure 1 The phase shift mask blank 10 shown in the figure has an etching mask film 40 on the phase shift film 30. Therefore, when manufacturing the phase shift mask blank 10, an etching mask film forming step is performed. In addition, when manufacturing a phase shift mask blank having an etching mask film 40 on the phase shift film 30 and an anti-etching film on the etching mask film 40, the anti-etching film is formed on the etching mask film 40 after the etching mask film forming step. Figure 2In the phase shift mask blank 10 shown, when manufacturing a phase shift mask blank including a resist film on the phase shift film 30 , the resist film is formed after the phase shift film forming step.

[0148] The phase shift mask blank 10 of the first embodiment has an etching mask film 40 formed on the phase shift film 30, and at least the phase shift film 30 has a columnar structure. In addition, the phase shift mask blank 10 of the second embodiment has a phase shift film 30 formed thereon, and the phase shift film 30 has a columnar structure.

[0149] In the phase shift mask blank 10 of the first and second embodiments, when the phase shift film 30 is patterned by wet etching, etching in the film thickness direction is promoted and side etching is suppressed, so that the cross-sectional shape is good, and a phase shift film pattern having a desired transmittance (for example, high transmittance) can be formed in a short etching time. Therefore, a phase shift mask blank capable of manufacturing a phase shift mask that can transfer a high-definition phase shift film pattern with good accuracy without reducing the transmittance of a transparent substrate due to damage to the substrate by a wet etching solution can be obtained.

[0150] In addition, when the phase shift film 30 is formed on the transparent substrate 20, the gas pressure in the film forming chamber during sputtering is 0.7 Pa or more and 2.4 Pa or less. By setting the range of the gas pressure in this way, the phase shift film 30 having an indentation hardness of 18 GPa or more and 23 GPa or less obtained by the nanoindentation method can be formed. By setting the indentation hardness of the phase shift film 30 to 18 GPa or more and 23 GPa or less, not only can the side etching during the pattern formation described later be suppressed, but also a high etching rate can be achieved, and the surface roughness of the transparent substrate 20 can be suppressed. Here, from the viewpoints of increasing the effect of suppressing the reduction of the wet etching rate by setting the indentation hardness to 18 GPa or more and 23 GPa or less, improving the cleaning resistance of the phase shift film 30, and facilitating the improvement of the transmittance, it is preferred that the atomic ratio of the transition metal to silicon in the transition metal silicide target is transition metal:silicon=1:3 or more and 1:15 or less as described above.

[0151] Implementation 3.4.

[0152] In Embodiments 3 and 4, a method for manufacturing a phase shift mask will be described.

[0153] Figure 3 It is an explanatory diagram showing a method for manufacturing a phase shift mask according to the third embodiment. Figure 4 It is an explanatory diagram showing a method for manufacturing a phase shift mask according to a fourth embodiment.

[0154] Figure 3 The phase shift mask is manufactured using Figure 1The method for manufacturing a phase shift mask using the phase shift mask blank 10 shown in the figure includes: forming a resist film on the etching mask film 40 of the phase shift mask blank 10 as follows; forming a resist film pattern 50 by drawing / developing a desired pattern on the resist film (a first resist film pattern forming step); wet etching the etching mask film 40 using the resist film pattern 50 as a mask to form an etching mask film pattern 40a on the phase shift film 30 (a first etching mask film pattern forming step); wet etching the phase shift film 30 using the etching mask film pattern 40a as a mask to form a phase shift film pattern 30a on the transparent substrate 20 (a phase shift film pattern forming step). In addition, the method also includes a second resist film pattern forming step and a second etching mask film pattern forming step.

[0155] Figure 4 The phase shift mask is manufactured using Figure 2 The method for manufacturing a phase shift mask using the phase shift mask blank 10 shown in the figure includes: a process of forming a resist film on the phase shift mask blank 10 as follows; forming a resist film pattern 50 by drawing / developing a desired pattern on the resist film (a first resist film pattern forming process); wet etching the phase shift film 30 using the resist film pattern 50 as a mask to form a phase shift film pattern 30a on a transparent substrate 20 (a phase shift film pattern forming process).

[0156] Hereinafter, each step of the process of manufacturing the phase shift mask of Embodiments 3 and 4 will be described in detail.

[0157] Phase shift mask manufacturing process according to Embodiment 3

[0158] 1. First resist film pattern forming step

[0159] In the first resist film pattern forming step, first, a resist film is formed on the etching mask film 40 of the phase shift mask blank 10 of the first embodiment. The resist film material used is not particularly limited. For example, it can be a material that is sensitive to a laser having any wavelength selected from the wavelength range of 350nm to 436nm as described later. In addition, the resist film can be either positive or negative.

[0160] Then, a desired pattern is drawn on the resist film using a laser having an arbitrary wavelength selected from the wavelength range of 350 nm to 436 nm. The pattern drawn on the resist film is the pattern formed on the phase shift film 30. Examples of the pattern drawn on the resist film include a line and space pattern and a hole pattern.

[0161] Then, the resist film is developed with a given developer, such as Figure 3 As shown in (a), a first resist film pattern 50 is formed on the etching mask film 40.

[0162] 2. First Etching Mask Film Pattern Forming Step

[0163] In the first etching mask film pattern forming step, first, the etching mask film 40 is etched using the first anti-etching film pattern 50 as a mask to form the first etching mask film pattern 40a. The etching mask film 40 is formed of a chromium-based material containing chromium (Cr). From the viewpoint of being able to accelerate the etching speed and suppress side etching, it is preferred that the etching mask film 40 has a columnar structure. The etching solution for etching the etching mask film 40 is not particularly limited as long as it can selectively etch the etching mask film 40. Specifically, an etching solution containing ammonium cerium nitrate and perchloric acid can be cited.

[0164] Then, use a resist stripping solution or by ashing, such as Figure 3 As shown in (b), the first resist film pattern 50 is peeled off. Depending on the situation, the following phase shift film pattern forming step may be performed without peeling off the first resist film pattern 50.

[0165] 3. Phase shift film pattern forming process

[0166] In the first phase shift film pattern forming step, the phase shift film 30 is wet-etched using the first etching mask film pattern 40a as a mask. Figure 3 (c) A phase shift film pattern 30a is formed. Examples of the phase shift film pattern 30a include a line and space pattern and a hole pattern. The etching solution for etching the phase shift film 30 is not particularly limited as long as it can selectively etch the phase shift film 30. For example, examples include an etching solution containing ammonium fluoride, phosphoric acid and hydrogen peroxide, and an etching solution containing ammonium hydrofluoride and hydrogen peroxide.

[0167] In order to make the cross-sectional shape of the phase shift film pattern 30a good, wet etching is preferably performed for a time (over-etching time) longer than the time (proper etching time) until the transparent substrate 20 is exposed in the phase shift film pattern 30a. The over-etching time is preferably set to a time obtained by adding 20% ​​of the proper etching time to the proper etching time, and more preferably to a time obtained by adding 10% of the proper etching time, in consideration of the influence on the transparent substrate 20, etc.

[0168] 4. Second resist film pattern forming step

[0169] In the second resist film pattern forming step, first, a resist film covering the first etching mask film pattern 40a is formed. The resist film material used is not particularly limited. For example, any material that is sensitive to a laser having any wavelength selected from the wavelength range of 350nm to 436nm described later can be used. In addition, the resist film can be either positive or negative.

[0170] Then, a desired pattern is drawn on the resist film using a laser having an arbitrary wavelength selected from the wavelength range of 350 nm to 436 nm. The pattern drawn on the resist film is a light-shielding band pattern for shielding the peripheral area of ​​the area where the pattern is formed on the phase shift film 30, a light-shielding band pattern for shielding the central part of the phase shift film pattern, etc. It should be noted that, depending on the transmittance of the phase shift film 30 to the exposure light, the pattern drawn on the resist film also includes a pattern without a light-shielding band pattern for shielding the central part of the phase shift film pattern 30a.

[0171] Then, the resist film is developed with a given developer, such as Figure 3 As shown in (d), a second resist film pattern 60 is formed on the first etching mask film pattern 40a.

[0172] 5. Second Etching Mask Film Pattern Formation Step

[0173] In the second etching mask film pattern forming step, the first etching mask film pattern 40a is etched using the second resist film pattern 60 as a mask. Figure 3 (e) shows the formation of the second etching mask film pattern 40b. The first etching mask film pattern 40a is formed of a chromium-based material containing chromium (Cr). The etching solution for etching the first etching mask film pattern 40a is not particularly limited as long as it can selectively etch the first etching mask film pattern 40a. For example, an etching solution containing ammonium cerium nitrate and perchloric acid can be cited.

[0174] Then, the second resist film pattern 60 is removed using a resist stripping solution or by ashing.

[0175] Thus, the phase shift mask 100 can be obtained.

[0176] It should be noted that, in the above description, the case where the etching mask film 40 has the function of blocking the transmission of exposure light is described, but in the case where the etching mask film 40 only has the function of a hard mask when etching the phase shift film 30, in the above description, the second anti-etching film pattern forming process and the second etching mask film pattern forming process are not performed, and the first etching mask film pattern is peeled off after the phase shift film pattern forming process to produce the phase shift mask 100.

[0177] According to the method for manufacturing a phase shift mask of the third embodiment, since the phase shift mask blank of the first embodiment is used, the etching time can be shortened, and a phase shift film pattern with a good cross-sectional shape can be formed. Therefore, a phase shift mask capable of transferring a high-definition phase shift film pattern with good accuracy can be manufactured. The phase shift mask manufactured in this way can cope with the miniaturization of line and space patterns and contact holes.

[0178] Phase shift mask manufacturing process according to Embodiment 4

[0179] 1. Resist film pattern forming process

[0180] In the resist film pattern forming step, first, a resist film is formed on the phase shift film 30 of the phase shift mask blank 10 of Embodiment 2. The resist film material used is the same as that described in Embodiment 3. It should be noted that, in order to achieve good adhesion with the phase shift film 30, the surface of the phase shift film 30 may be subjected to surface modification treatment as needed before the resist film is formed. After the resist film is formed in the same manner as described above, a desired pattern is drawn on the resist film using a laser having an arbitrary wavelength selected from the wavelength range of 350 nm to 436 nm. Then, the resist film is developed using a given developer, such as Figure 4 As shown in (a), a resist film pattern 50 is formed on the phase shift film 30.

[0181] 2. Phase shift film pattern forming process

[0182] In the phase shift film pattern forming process, the phase shift film 30 is etched using the resist film pattern as a mask. Figure 4 As shown in (b), a phase shift film pattern 30a is formed. The etching solution for etching the phase shift film pattern 30a and the phase shift film 30 and the over-etching time are the same as those described in the third embodiment.

[0183] Then, the resist film pattern 50 is removed using a resist stripping solution or by ashing ( Figure 4 (c)).

[0184] Thus, the phase shift mask 100 can be obtained.

[0185] According to the method for manufacturing a phase shift mask of this embodiment 4, since the phase shift mask blank of embodiment 2 is used, the etching time can be shortened, and a phase shift film pattern with a good cross-sectional shape can be formed without causing a decrease in the transmittance of the transparent substrate due to damage to the substrate by a wet etching solution. Therefore, a phase shift mask capable of transferring a high-precision phase shift film pattern with good accuracy can be manufactured. The phase shift mask manufactured in this way can cope with the miniaturization of line and space patterns and contact holes. In addition, when a phase shift mask is manufactured using a phase shift mask blank having a phase shift film 30 with an indentation hardness of 18 GPa or more and 23 GPa or less obtained by a nanoindentation method, in addition to the above-mentioned effects, the surface roughness of the transparent substrate 20 can be suppressed, and the cleaning resistance of the phase shift film 30 can be improved.

[0186] Implementation method 5.

[0187] In Embodiment 5, a method for manufacturing a display device is described. The display device can be manufactured by a process (mask placement process) of using a phase shift mask 100 manufactured using the above-mentioned phase shift mask blank 10 or by the above-mentioned method for manufacturing the phase shift mask 100 and a process (exposure process) of transferring a transfer pattern to a resist film on the display device by exposure.

[0188] Hereinafter, each step will be described in detail.

[0189] 1. Placement process

[0190] In the placement step, the phase shift mask manufactured in Embodiment 3 is placed on a mask stage of an exposure device. Here, the phase shift mask is arranged to face the resist film formed on the display device substrate via the projection optical system of the exposure device.

[0191] 2. Pattern transfer process

[0192] In the pattern transfer process, the phase shift mask 100 is irradiated with exposure light to transfer the phase shift film pattern to the resist film formed on the display device substrate. The exposure light can be a composite light containing a plurality of wavelengths selected from the wavelength range of 365nm to 436nm, or a monochromatic light selected by removing a certain wavelength range from the wavelength range of 365nm to 436nm using a filter. For example, the exposure light is a composite light containing i-line, h-line and g-line, or i-line monochromatic light. When the composite light is used as the exposure light, the exposure light intensity can be increased to increase the luminous flux, thereby reducing the manufacturing cost of the display device.

[0193] According to the method for manufacturing a display device of Embodiment 3, a high-definition display device having a high resolution, a fine line and space pattern, and a contact hole can be manufactured.

[0194] It should be noted that, in the above embodiments, as the photomask blank having a pattern forming film and the photomask having a transfer pattern, a phase shift mask blank having a phase shift mask film and a phase shift mask having a phase shift mask film pattern are described, but the present invention is not limited thereto. For example, the present invention can also be applied to a binary mask blank having a light shielding film as a pattern forming film and a binary mask having a light shielding film pattern.

[0195] Example

[0196] Example 1.

[0197] A. Phase-Shift Mask Blanks and Methods of Making Them

[0198] In order to manufacture the phase shift mask blank of Example 1, first, a synthetic quartz glass substrate of 1214 size (1220 mm×1400 mm) was prepared as the transparent substrate 20 .

[0199] Then, the synthetic quartz glass substrate is placed on a tray (not shown) with the main surface facing downward, and is transported into the chamber of the inline sputtering apparatus.

[0200] In order to form the phase shift film 30 on the main surface of the transparent substrate 20, first, an inert gas composed of argon (Ar), nitrogen (N2), and helium (He) (Ar: 18 sccm, N2: 13 sccm, He: 50 sccm) was introduced while the sputtering gas pressure in the first chamber was set to 1.6 Pa. Then, a sputtering power of 7.6 kW was applied to the first sputtering target material containing molybdenum and silicon (molybdenum: silicon = 1:9), and a nitride of molybdenum silicide containing molybdenum, silicon, and nitrogen was deposited on the main surface of the transparent substrate 20 by reactive sputtering. Then, the phase shift film 30 with a film thickness of 150 nm was formed.

[0201] Next, the transparent substrate 20 with the phase shift film 30 was transported to the second chamber, and a mixed gas of argon (Ar) and nitrogen (N2) (Ar: 65 sccm, N2: 15 sccm) was introduced into the second chamber. Then, a sputtering power of 1.5 kW was applied to the second sputtering target containing chromium, and chromium nitride (CrN) containing chromium and nitrogen (film thickness 15 nm) was formed on the phase shift film 30 by reactive sputtering. Next, in a state where a predetermined vacuum degree was set in the third chamber, a mixed gas (30 sccm) of argon (Ar) gas and methane (CH4: 4.9%) gas was introduced, and a sputtering power of 8.5 kW was applied to the third sputtering target containing chromium, and chromium carbide (CrC) containing chromium and carbon (film thickness 60 nm) was formed on CrN by reactive sputtering. Finally, in the state where the fourth chamber is set to a given vacuum degree, a mixed gas of argon (Ar) and methane (CH4: 5.5%) gas and a mixed gas of nitrogen (N2) and oxygen (O2) (Ar+CH4: 30 sccm, N2: 8 sccm, O2: 3 sccm) are introduced, and a sputtering power of 2.0 kW is applied to the fourth sputtering target containing chromium, and chromium carbonitride (CrCON) containing chromium, carbon, oxygen and nitrogen (film thickness 30 nm) is formed on CrC by reactive sputtering. As described above, an etching mask film 40 having a stacked structure of a CrN layer, a CrC layer and a CrCON layer is formed on the phase shift film 30.

[0202] Thus, the phase shift mask blank 10 in which the phase shift film 30 and the etching mask film 40 are formed on the transparent substrate 20 is obtained.

[0203] The transmittance and phase difference of the phase shift film 30 (the surface of the phase shift film 30) of the obtained phase shift mask blank 10 were measured using MPM-100 manufactured by Lasertec. In the measurement of the transmittance and phase difference of the phase shift film 30, a substrate with a phase shift film (model substrate) in which the phase shift film 30 was formed on the main surface of a synthetic quartz glass substrate was used. The substrate with a phase shift film (model substrate) was mounted on the same tray. Before forming the etching mask film 40, the substrate with a phase shift film (model substrate) was taken out from the chamber, and the transmittance and phase difference of the phase shift film 30 were measured. As a result, the transmittance was 27% (wavelength: 405nm) and the phase difference was 178° (wavelength: 405nm).

[0204] In addition, the obtained phase shift mask blank 10 was subjected to composition analysis in the depth direction by X-ray photoelectron spectroscopy (XPS).

[0205] As a result of the composition analysis in the depth direction of the phase shift mask blank 10 by XPS, in the phase shift film 30, except for the composition gradient region at the interface between the transparent substrate 20 and the phase shift film 30 and the composition gradient region at the interface between the phase shift film 30 and the etching mask film 40, the content of each constituent element in the depth direction is basically constant, Mo is 8 atomic%, Si is 40 atomic%, N is 48 atomic%, and O is 4 atomic%. In addition, the atomic ratio of molybdenum to silicon is 1:5, which is within the range of 1:3 or more and 1:15 or less. In addition, the total content of oxygen and nitrogen as light elements is 52 atomic%, which is within the range of 50 atomic% or more and 65 atomic% or less. It should be noted that it can be considered that the oxygen contained in the phase shift film 30 is because the sputtering gas pressure is as high as 0.8 Pa or more and there is a trace amount of oxygen in the chamber during film formation.

[0206] Furthermore, the indentation hardness of the obtained phase shift film 30 was measured (the measuring method will be described later), and the indentation hardness was found to satisfy a range of 18 GPa to 23 GPa.

[0207] Next, a cross-sectional SEM (scanning electron microscope) observation was performed at a magnification of 80,000 times at the central position of the transfer pattern forming area of ​​the obtained phase shift mask blank 10, and the result confirmed that the phase shift film 30 has a columnar structure. That is, it can be confirmed that the particles of the molybdenum silicide compound constituting the phase shift film 30 have a columnar particle structure extending in the film thickness direction of the phase shift film 30. It can also be confirmed that the columnar particle structure of the phase shift film 30 is in a state where columnar particles in the film thickness direction are irregularly formed and the lengths of the columnar particles in the film thickness direction are inconsistent. In addition, it can be confirmed that the sparse portion of the phase shift film 30 is continuously formed in the film thickness direction. In addition, for the image obtained by the cross-sectional SEM observation, image data of 64 pixels in length and 256 pixels in width were extracted for the area including the center portion in the thickness direction of the phase shift film 30 ( Figure 5(a)). Furthermore, Figure 5 The image data shown was Fourier transformed ( Figure 5 (b)). It was confirmed that in the spatial spectrum distribution obtained by Fourier transform, the signal intensity (maximum signal intensity) at the origin of the spatial frequency was 3136000, and in addition to the above-mentioned maximum signal intensity, there was also a spatial spectrum with a signal intensity of 66150. The maximum signal intensity corresponding to the origin of the spatial frequency is 66150 / 3136000=0.021 (i.e., 2.1%), and the phase shift film 30 is a columnar structure with a signal intensity of 1.0% or more.

[0208] In addition, for Figure 5 (b) The Fourier transformed image above is obtained by changing the origin of the spatial frequency, i.e. Figure 5 When the center of the image of (b) is set as the origin (0) and the maximum spatial frequency corresponding to both ends of the horizontal axis 256 pixels is set as 1 (100%), the signal having a signal intensity of 2.1% relative to the maximum signal intensity corresponding to the origin of the above spatial frequency is the phase shift film 30 having a columnar structure, and the columnar structure has a signal at a position 0.055, that is, 5.5% away from the above origin. It should be noted that the same is true in the Fourier transform images of the following examples and comparative examples.

[0209] In addition, a plate-like sample with a thickness of 100 nm (in-plane direction of the substrate) perpendicular to the film thickness direction was collected near the film thickness center of the phase shift film 30, and dark field plan STEM observation was performed. The dark field plan STEM (scanning transmission electron microscope) observation results are shown in FIG. Figure 6 .like Figure 6 As shown, gray-white and gray-black streaks were observed in what are believed to be columnar particle portions (gray-white portions) and between particles (gray-black portions). For the gray-white and gray-black portions, the elements (Mo, Si, N, O) constituting the phase shift film 30 were quantitatively analyzed by EDX analysis (energy dispersive X-ray analysis) (not shown). The results confirmed that in the gray-black portion and the gray-white portion, the detected amount (count) of Si was higher than that of Mo, and that the detected amount (count) of the constituent elements of the phase shift film 30 in the gray-black portion was lower than the detected amount (count) of the constituent elements of the phase shift film 30 in the gray-white portion. In particular, the detected amount (count) of Si in the gray-black portion was 600 (Counts), and the detected amount (count) of Si in the gray-white portion was 400 (Counts), and the difference in the detected amount (count) was large compared to other elements. Based on the results, it can be confirmed that the phase shift film 30 forms a particle portion (gray-white portion) with a relatively high density and a sparse portion (gray-black portion) with a relatively low density. The particle portion corresponds to Figure 5 , Figure 7It should be noted that the film density of the entire phase shift film 30 is lower than the film density of the conventional phase shift film.

[0210] B. Phase-Shift Mask and Method of Making the Same

[0211] In order to manufacture the phase-shift mask 100 using the phase-shift mask blank 10 manufactured as described above, first, a photoresist film is applied on the etching mask film 40 of the phase-shift mask blank 10 using a resist coating apparatus.

[0212] Then, through a heating / cooling process, a photoresist film with a film thickness of 520 nm was formed.

[0213] Then, the photoresist film was patterned using a laser drawing device, and after a development / rinsing process, a resist film pattern having a hole pattern with a hole diameter of 1.5 μm was formed on the etching mask film.

[0214] Then, the etching mask film is wet-etched using a chromium etching solution containing ammonium cerium nitrate and perchloric acid, using the resist film pattern as a mask, thereby forming a first etching mask film pattern 40 a .

[0215] Then, the phase shift film 30 is wet-etched using the first etching mask film pattern 40a as a mask with a molybdenum silicide etching solution obtained by diluting a mixed solution of ammonium hydrofluoride and hydrogen peroxide with pure water, thereby forming a phase shift film pattern 30a. In order to make the cross-sectional shape vertical and to form a required fine pattern, the wet etching is performed with an overetching time of 110%. The appropriate etching time in Example 1 is 0.15 times the appropriate etching time in the comparative example described later, and the etching time can be greatly shortened.

[0216] Then, the resist film pattern is peeled off.

[0217] Then, a photoresist film is applied using a resist coating apparatus so as to cover the first etching mask film pattern 40 a .

[0218] Then, through a heating / cooling process, a photoresist film with a film thickness of 520 nm was formed.

[0219] Then, a photoresist film is drawn using a laser drawing device, and after a development / rinsing process, a second resist film pattern 60 for forming a light shielding band is formed on the first etching mask film pattern 40a.

[0220] Then, the first etching mask film pattern 40 a formed in the transfer pattern formation region was wet-etched using the second resist film pattern 60 as a mask with a chromium etching solution containing ammonium cerium nitrate and perchloric acid.

[0221] Then, the second resist film pattern 60 is peeled off.

[0222] Thus, a phase shift mask 100 is obtained, wherein a phase shift film pattern 30 a having an aperture of 1.5 μm is provided in a transfer pattern forming region on a transparent substrate 20 , and a light shielding film having a stacked structure of the phase shift film pattern 30 a and an etching mask film pattern 40 b is formed on the transparent substrate 20 .

[0223] The cross section of the obtained phase-shift mask was observed using a scanning electron microscope. The cross section of the phase-shift film pattern is composed of the upper surface, lower surface and side surface of the phase-shift film pattern. The angle of the cross section of the phase-shift film pattern refers to the angle formed by the portion where the upper surface of the phase-shift film pattern is connected to the side surface (upper side) and the portion where the side surface is connected to the lower surface (lower side). The cross section angle of the phase-shift film pattern 30a of the obtained phase-shift mask is 74°, and has a cross-sectional shape that is close to vertical. The phase-shift film pattern 30a formed in the phase-shift mask of Example 1 has a cross-sectional shape that can fully exert the phase shift effect. By making the phase-shift film 30 have a columnar structure, the phase-shift film pattern 30a forms a good cross-sectional shape, which can be considered to be due to the following mechanism. According to Figure 7 The observation result of the cross-sectional SEM photograph of the phase shift film 30 shows that the phase shift film 30 has a columnar particle structure (columnar structure), and columnar particles extending in the film thickness direction are irregularly formed. Figure 6 Observation results of dark field planar STEM photos, Figure 7 According to the observation results of the cross-sectional SEM photograph, the phase shift film 30 forms a relatively high-density columnar particle portion and a relatively low-density sparse portion. Based on these facts, it can be considered that when the phase shift film 30 is patterned by wet etching, the etching liquid penetrates into the sparse portion in the phase shift film 30, making it easy to etch along the film thickness direction. On the other hand, since columnar particles are irregularly formed in the direction perpendicular to the film thickness direction (the direction within the substrate surface) and the sparse portion in this direction is intermittently formed, it is difficult to etch in this direction and the side etching is suppressed. Therefore, the phase shift film pattern 30a obtains a good cross-sectional shape close to vertical. In addition, for the phase shift film pattern, no penetration is observed at the interface with the etching mask film pattern and the interface with the substrate. Therefore, for the exposure light containing light in the wavelength range of 300nm or more and 500nm or less, more specifically, for the exposure light containing the composite light of i-line, h-line and g-line, a phase shift mask with excellent phase shift effect is obtained.

[0224] Therefore, when the phase shift mask of Example 1 is set on the mask stage of an exposure device and the resist film to be transferred to the display device is exposed, a fine pattern of less than 2.0 μm can be transferred with high accuracy.

[0225] It should be noted that Figure 7The cross-sectional SEM photograph of is a cross-sectional SEM photograph of the phase shift mask manufacturing process of Example 1, in which the first etching mask film pattern 40a is used as a mask, the phase shift film 30 is wet-etched (110% overetching) using a molybdenum silicide etching solution to form the phase shift film pattern 30a, and the resist film pattern is peeled off. Figure 7 As shown, the phase shift film pattern 30a maintains the columnar structure of the phase shift film 30, and the surface of the transparent substrate 20 exposed after the phase shift film 30 is removed is smooth, and the transmittance reduction caused by the rough surface of the transparent substrate 20 can be ignored.

[0226] Example 2.

[0227] A. Phase-Shift Mask Blanks and Methods of Making Them

[0228] In order to manufacture the phase shift mask blank of Example 2, a synthetic quartz glass substrate of 1214 size (1220 mm×1400 mm) was prepared as a transparent substrate in the same manner as in Example 1.

[0229] The synthetic quartz glass substrate was transported to the chamber of the inline sputtering device by the same method as in Example 1. The same sputtering target materials as in Example 1 were used as the first sputtering target, the second sputtering target, the third sputtering target, and the fourth sputtering target. Then, with the sputtering gas pressure in the first chamber set to 1.6 Pa, a mixed gas (Ar: 18 sccm, N2: 15 sccm, He: 50 sccm, NO: 4 sccm) of an inert gas composed of argon (Ar), helium (He) and nitrogen (N2) and a nitric oxide gas (NO) as a reactive gas was introduced. Then, a sputtering power of 7.6 kW was applied to the first sputtering target containing molybdenum and silicon (molybdenum: silicon = 1:9), and a nitride oxide of molybdenum silicide containing molybdenum, silicon, oxygen and nitrogen was deposited on the main surface of the transparent substrate 20 by reactive sputtering. Then, a phase shift film 30 with a film thickness of 140 nm was formed.

[0230] Then, after the phase shift film is formed on the transparent substrate, it is taken out of the chamber and the surface of the phase shift film is cleaned with pure water at a temperature of 30 degrees and a cleaning time of 60 seconds.

[0231] Then, by the same method as in Example 1, an etching mask film 40 was formed.

[0232] Thus, the phase shift mask blank 10 in which the phase shift film 30 and the etching mask film 40 are formed on the transparent substrate 20 is obtained.

[0233] The transmittance and phase difference of the phase shift film of the obtained phase shift mask blank 10 (the surface of the phase shift film was cleaned with pure water) were measured using MPM-100 manufactured by Lasertec. The transmittance and phase difference of the phase shift film were measured using a substrate with a phase shift film (model substrate) in which the phase shift film 30 was formed on the main surface of a synthetic quartz glass substrate, and the substrate with a phase shift film was mounted on the same tray. The substrate with a phase shift film (model substrate) was taken out from the chamber before the etching mask film was formed, and the transmittance and phase difference of the phase shift film 30 were measured. As a result, the transmittance was 33% (wavelength: 365nm) and the phase difference was 169 degrees (wavelength: 365nm).

[0234] In addition, the obtained phase shift mask blank was subjected to composition analysis in the depth direction by X-ray photoelectron spectroscopy (XPS).

[0235] As a result, similarly to Example 1, in the phase shift film 30, except for the composition gradient region at the interface between the transparent substrate 20 and the phase shift film 30 and the composition gradient region at the interface between the phase shift film 30 and the etching mask film 40, the content of each constituent element in the depth direction is substantially constant, and Mo is 7 atomic%, Si is 38 atomic%, N is 45 atomic%, and O is 10 atomic%. In addition, the atomic ratio of molybdenum to silicon is 1:5.4, which is within the range of 1:3 or more and 1:15 or less. In addition, the total content of oxygen, nitrogen, and carbon as light elements is 55 atomic%, which is within the range of 50 atomic% or more and 65 atomic% or less.

[0236] Next, a cross-sectional SEM observation was performed at a magnification of 80,000 times at the central position of the transfer pattern forming area of ​​the obtained phase shift mask blank 10, and the result confirmed that the phase shift film 30 has a columnar structure. That is, it can be confirmed that the particles of the molybdenum silicide compound constituting the phase shift film 30 have a columnar particle structure extending in the film thickness direction of the phase shift film 30. It can also be confirmed that the columnar particle structure of the phase shift film 30 is in a state where columnar particles in the film thickness direction are irregularly formed and the lengths of the columnar particles in the film thickness direction are inconsistent. In addition, it can be confirmed that the sparse portion of the phase shift film 30 is continuously formed in the film thickness direction. In addition, for the image obtained by the cross-sectional SEM observation, image data of 64 pixels in length and 256 pixels in width were extracted for the area including the center portion in the thickness direction of the phase shift film 30 ( Figure 8 (a)). Furthermore, Figure 8 The image data shown in (a) is Fourier transformed ( Figure 8(b)). It was confirmed that in the spatial spectrum distribution obtained by Fourier transform, the signal intensity (maximum signal intensity) at the origin of the spatial frequency was 2406000, and in addition to the above-mentioned maximum signal intensity, there was a spatial spectrum with a signal intensity of 39240. The maximum signal intensity corresponding to the origin of the spatial frequency is 39240 / 2406000=0.016 (i.e., 1.6%), and the phase shift film 30 is a columnar structure with a signal intensity of 1.0% or more.

[0237] In addition, for Figure 8 (b) is the Fourier transformed image, when the origin of the spatial frequency, i.e. Figure 8 When the center of the image of (b) is set as the origin (0) and the two ends of the horizontal axis 256 pixels are set as 1 (100%), the signal with a signal intensity of 1.6% relative to the maximum signal intensity corresponding to the origin of the above-mentioned spatial frequency is the phase shift film 30 having a columnar structure, and the columnar structure has a signal at a position 0.023, that is, 2.3% away from the above-mentioned origin.

[0238] In addition, dark field plan STEM observation was performed near the film thickness center of the phase shift film 30 in the same manner as in Example 1. As a result, it was confirmed that, in the same manner as in Example 1, each columnar particle portion and a sparse portion were formed in the phase shift film 30 .

[0239] B. Phase-Shift Mask and Method of Making the Same

[0240] Using the phase shift mask blank manufactured as described above, a phase shift mask having a phase shift film pattern with a hole diameter of 1.5 μm was manufactured by the same method as in Example 1. In order to make the cross-sectional shape vertical and to form the required fine pattern, the wet etching of the phase shift film 30 was performed with an overetching time of 110%. The appropriate etching time in Example 2 is 0.07 times the appropriate etching time in the comparative example described later, and the etching time can be greatly shortened.

[0241] The cross section of the obtained phase shift mask was observed using a scanning electron microscope. The cross section of the phase shift film pattern 30a of the phase shift mask had an angle of 74° and had a cross-sectional shape close to vertical. In addition, for the phase shift film pattern, no penetration was observed at the interface with the etching mask film pattern and the interface with the substrate. Therefore, for exposure light including light in the wavelength range of 300nm to 500nm, more specifically, for exposure light including composite light of i-line, h-line and g-line, a phase shift mask having an excellent phase shift effect was obtained.

[0242] Therefore, when the phase shift mask of Example 2 is set on the mask stage of an exposure device and the resist film to be transferred to the display device is exposed, a fine pattern of less than 2.0 μm can be transferred with high accuracy.

[0243] It should be noted that Fig. 9 The cross-sectional SEM photograph of is a cross-sectional SEM photograph of the phase shift mask manufacturing process of Example 2, in which the first etching mask film pattern 40a is used as a mask, the phase shift film 30 is wet-etched (110% overetching) using a molybdenum silicide etching solution to form the phase shift film pattern 30a, and the resist film pattern is peeled off. Fig. 9 As shown, the phase shift film pattern 30a maintains the columnar structure of the phase shift film 30, and the surface of the transparent substrate 20 exposed after the phase shift film 30 is removed is smooth, and the transmittance reduction caused by the rough surface of the transparent substrate 20 can be ignored.

[0244] Example 3.

[0245] A. Phase-Shift Mask Blanks and Methods of Making Them

[0246] The phase-shift mask blank of Example 3 is a phase-shift mask blank that does not have the etching mask film in the phase-shift mask blank of Example 1.

[0247] In order to manufacture the phase shift mask blank of Example 3, a synthetic quartz glass substrate of 1214 size (1220 mm×1400 mm) was prepared as the transparent substrate 20 in the same manner as in Example 1.

[0248] In order to form the phase shift film 30 on the main surface of the transparent substrate 20 using the same film forming method as in Example 1, first, an inert gas composed of argon (Ar), nitrogen (N2), and helium (He) (Ar: 18 sccm, N2: 13.5 sccm, He: 50 sccm) was introduced while the sputtering gas pressure in the first chamber was set to 1.4 Pa. Under these film forming conditions, a phase shift film 30 (film thickness: 150 nm) composed of oxynitride of molybdenum silicide was formed on the transparent substrate 20.

[0249] Thus, the phase shift mask blank 10 in which the phase shift film 30 is formed on the transparent substrate 20 is obtained.

[0250] The transmittance and phase difference of the phase shift film of the obtained phase shift mask blank 10 were measured using MPM-100 manufactured by Lasertec. In the measurement of the transmittance and phase difference of the phase shift film, a substrate with a phase shift film (model substrate) in which the phase shift film 30 was formed on the main surface of a synthetic quartz glass substrate was used, and the substrate with a phase shift film was mounted on the same tray. As a result, the transmittance was 24% (wavelength: 405nm) and the phase difference was 183 degrees (wavelength: 405nm).

[0251] The phase shift film 30 of the obtained phase shift mask blank 10 was subjected to a composition analysis in the depth direction by X-ray photoelectron spectroscopy (XPS). As a result, the content of each constituent element in the depth direction of the phase shift film 30 was substantially constant, as in Example 1. In addition, the atomic ratio of molybdenum to silicon was 1:5, which was within the range of 1:3 or more and 1:15 or less. In addition, the total content of oxygen, nitrogen, and carbon as light elements was 52 atomic %, which was within the range of 50 atomic % or more and 65 atomic % or less. In addition, the content of oxygen was 0.3 atomic %, which was within the range of greater than 0 atomic % and 40 atomic % or less.

[0252] Next, a cross-sectional SEM observation was performed at a magnification of 80,000 times at the central position of the transfer pattern forming area of ​​the obtained phase shift mask blank 10, and the result confirmed that the phase shift film 30 has a columnar structure. That is, it can be confirmed that the particles of the molybdenum silicide compound constituting the phase shift film 30 have a columnar particle structure extending in the film thickness direction of the phase shift film 30. It can also be confirmed that the columnar particle structure of the phase shift film 30 is in a state where columnar particles in the film thickness direction are irregularly formed and the lengths of the columnar particles in the film thickness direction are inconsistent. In addition, it can be confirmed that the sparse portion of the phase shift film 30 is continuously formed in the film thickness direction. In addition, for the image obtained by the cross-sectional SEM observation, image data of 64 pixels in length and 256 pixels in width were extracted for the area including the center portion in the thickness direction of the phase shift film 30 ( Fig.10 (a)). Furthermore, Fig.10 The image data shown in (a) is Fourier transformed ( Fig.10 (b)). It was confirmed that in the spatial spectrum distribution obtained by Fourier transform, the signal intensity (maximum signal intensity) at the origin of the spatial frequency was 31590000, and in addition to the above maximum signal intensity, there was a spatial spectrum with a signal intensity of 47230. The maximum signal intensity corresponding to the origin of the spatial frequency is 47230 / 3159000=0.015 (i.e., 1.5%), and the phase shift film 30 is a columnar structure with a signal intensity of 1.0% or more.

[0253] In addition, for Fig.10 (b) is the Fourier transformed image, when the origin of the spatial frequency, i.e. Fig.10 When the center of the image of (b) is set as the origin (0) and the two ends of the horizontal axis 256 pixels are set as 1 (100%), the signal with a signal intensity of 1.5% relative to the maximum signal intensity corresponding to the origin of the above-mentioned spatial frequency is the phase shift film 30 having a fine columnar structure with a large spatial frequency, and the columnar structure has a signal at a position 0.078, that is, 7.8% away from the above-mentioned origin.

[0254] In addition, dark field plan STEM observation was performed near the film thickness center of the phase shift film 30 in the same manner as in Example 1. As a result, it was confirmed that, in the same manner as in Example 1, columnar particles and sparse portions were formed in the phase shift film 30 .

[0255] B. Phase-Shift Mask and Method of Making the Same

[0256] Using the phase shift mask blank 10 manufactured as described above, a phase shift mask having a phase shift film pattern with a pore size of 1.5 μm was manufactured by the same method as in Example 1. In order to make the cross-sectional shape vertical and to form the required fine pattern, the wet etching of the phase shift film 30 was performed with an overetching time of 110%. The appropriate etching time in Example 3 is 0.20 times the appropriate etching time in the comparative example described later, and the etching time can be greatly shortened.

[0257] The cross section of the obtained phase shift mask was observed using a scanning electron microscope. The cross section of the phase shift film pattern 30a of the phase shift mask had an angle of 80° and had a cross-sectional shape close to vertical. In addition, for the phase shift film pattern, no penetration was observed at the interface with the etching mask film pattern and the interface with the substrate. Therefore, for exposure light including light in the wavelength range of 300nm to 500nm, more specifically, for exposure light including composite light of i-line, h-line and g-line, a phase shift mask having an excellent phase shift effect was obtained.

[0258] Therefore, when the phase shift mask of Example 3 is set on the mask stage of an exposure device and the resist film to be transferred to the display device is exposed, a fine pattern of less than 2.0 μm can be transferred with high accuracy.

[0259] It should be noted that Fig.11 The cross-sectional SEM photograph of is a cross-sectional SEM photograph of the phase shift mask manufacturing process of Example 3, in which the first etching mask film pattern 40a is used as a mask, the phase shift film 30 is wet-etched (110% overetching) using a molybdenum silicide etching solution to form the phase shift film pattern 30a, and the resist film pattern is peeled off. Fig.11 As shown, the phase shift film pattern 30a maintains the columnar structure of the phase shift film 30, and the surface of the transparent substrate 20 exposed after the phase shift film 30 is removed is smooth, and the transmittance reduction caused by the surface roughness of the transparent substrate 20 can be ignored. The line edge roughness is better than that of Example 1.

[0260] It should be noted that, in the above-mentioned embodiments, the case where molybdenum is used as the transition metal is described, but the same effects as those described above can be obtained in the case of other transition metals.

[0261] In addition, in the above-mentioned embodiments, examples of phase shift mask blanks and phase shift masks for display device manufacturing are described, but the invention is not limited thereto. The phase shift mask blanks and phase shift masks of the present invention can also be applied to semiconductor device manufacturing, MEMS manufacturing, printed circuit board applications, etc. In addition, the present invention can also be applied to binary mask blanks having a light shielding film as a thin film for pattern formation and binary masks having a light shielding film pattern.

[0262] In addition, in the above-mentioned embodiment, an example in which the size of the transparent substrate is 1214 size (1220mm×1400mm×13mm) is described, but it is not limited to this. In the case of a phase shift mask blank for display device manufacturing, a large size transparent substrate can be used, and the size of the transparent substrate is a side length of 300mm or more. The size of the transparent substrate used in the phase shift mask blank for display device manufacturing is, for example, 330mm×450mm or more and 2280mm×3130mm or less.

[0263] In addition, in the case of phase-shift mask blanks for semiconductor device manufacturing, MEMS manufacturing, and printed circuit board applications, a small-sized transparent substrate can be used, the size of which is a side length of 9 inches or less. The size of the transparent substrate used in the phase-shift mask blanks for the above-mentioned purposes is, for example, 63.1 mm × 63.1 mm or more and 228.6 mm × 228.6 mm or less. Usually, 6025 size (152 mm × 152 mm) and 5009 size (126.6 mm × 126.6 mm) are used for semiconductor manufacturing and MEMS manufacturing, and 7012 size (177.4 mm × 177.4 mm) and 9012 size (228.6 mm × 228.6 mm) are used for printed circuit boards.

[0264] Comparative Example 1.

[0265] A. Phase-Shift Mask Blanks and Methods of Making Them

[0266] In order to manufacture the phase shift mask blank of Comparative Example 1, a synthetic quartz glass substrate of 1214 size (1220 mm×1400 mm) was prepared as a transparent substrate in the same manner as in Example 1.

[0267] The synthetic quartz glass substrate was transported to the chamber of the inline sputtering device by the same method as in Example 1. Then, a mixed gas of argon (Ar) gas and nitrogen (N2) gas (Ar: 30 sccm, N2: 30 sccm) was introduced while the sputtering gas pressure in the first chamber was set to 0.5 Pa. Then, a sputtering power of 7.6 kW was applied to the first sputtering target material containing molybdenum and silicon (molybdenum: silicon = 1:9), and a nitride of molybdenum silicide containing molybdenum, silicon and nitrogen was deposited on the main surface of the transparent substrate by reactive sputtering. Thus, a phase shift film with a film thickness of 144 nm was formed.

[0268] The indentation hardness of the phase shift film of Comparative Example 1 does not satisfy 18 GPa or more and 23 GPa or less.

[0269] Then, by the same method as in Example 1, an etching mask film was formed.

[0270] Thus, a phase shift mask blank in which a phase shift film and an etching mask film are formed on a transparent substrate is obtained.

[0271] The transmittance and phase difference of the phase shift film of the obtained phase shift mask blank were measured using MPM-100 manufactured by Lasertec. The transmittance and phase difference of the phase shift film were measured using a substrate with a phase shift film (model substrate) in which a phase shift film was formed on the main surface of a synthetic quartz glass substrate, and the substrate with a phase shift film was mounted on the same tray. The substrate with a phase shift film (model substrate) was taken out of the chamber before forming the etching mask film, and the transmittance and phase difference of the phase shift film were measured. The results showed that the transmittance was 30% (wavelength: 405nm) and the phase difference was 177 degrees (wavelength: 405nm).

[0272] In addition, the obtained phase shift mask blank was subjected to composition analysis in the depth direction by X-ray photoelectron spectroscopy (XPS). As a result, in the phase shift film 30, except for the composition gradient region at the interface between the transparent substrate 20 and the phase shift film 30 and the composition gradient region at the interface between the phase shift film 30 and the etching mask film 40, the content of each constituent element in the depth direction was basically constant, Mo was 8 atomic%, Si was 39 atomic%, N was 52 atomic%, and O was 1 atomic%. In addition, the atomic ratio of molybdenum to silicon was 1:4.9, which was within the range of 1:3 or more and 1:15 or less. In addition, the total content of oxygen, nitrogen, and carbon as light elements was 53 atomic%, which was within the range of 50 atomic% or more and 65 atomic% or less.

[0273] Next, a cross-sectional SEM observation was performed at a magnification of 80,000 times at the central position of the transfer pattern formation area of ​​the obtained phase shift mask blank 10. As a result, no columnar structure was confirmed in the phase shift film, and it was confirmed that it was an ultrafine crystal structure or an amorphous structure. For the image obtained by the cross-sectional SEM observation, image data of 64 pixels in length and 256 pixels in width were extracted for the area including the center part in the thickness direction of the phase shift film 30 ( Fig.12 (a)). Furthermore, Fig.12 The image data shown in (a) is Fourier transformed ( Fig.12 (b)). In the spatial spectrum distribution obtained by Fourier transform, the signal intensity (maximum signal intensity) at the origin of the spatial frequency is 2073000, and no strong signal is confirmed other than the above maximum intensity signal, and there is only a spatial spectrum with a signal intensity of 12600. The maximum signal intensity corresponding to the origin of the spatial frequency is 12600 / 2073000=0.006 (i.e., 0.6%), and the phase shift film 30 is an ultrafine crystal structure or an amorphous structure that does not have a signal intensity of 1.0% or more.

[0274] B. Phase-Shift Mask and Method of Making the Same

[0275] Using the phase shift mask blank manufactured as described above, a phase shift mask was manufactured by the same method as in Example 1. In order to make the cross-sectional shape vertical and to form the required fine pattern, the wet etching of the phase shift mask was performed with an overetching time of 110%. The appropriate etching time in Comparative Example 1 was 142 minutes, which was a very long time.

[0276] in addition, Fig.13 The cross-sectional SEM photograph of FIG. 1 is a cross-sectional SEM photograph of the phase shift mask manufacturing process of the comparative example, in which the first etching mask film pattern 40a is used as a mask, the phase shift film 30 is wet-etched (110% overetching) using a molybdenum silicide etching solution to form the phase shift film pattern 30a, and before the resist film pattern is peeled off. Fig.13 As shown in FIG. 1 , the surface of the transparent substrate 20 exposed after the phase shift film 30 is removed is rough and appears cloudy when observed with the naked eye. Therefore, the decrease in transmittance caused by the rough surface of the transparent substrate 20 is significant.

[0277] Therefore, it is predicted that when the phase shift mask of Comparative Example 1 is set on the mask stage of an exposure device and the resist film to be transferred to the display device is exposed, a fine pattern smaller than 2.0 μm cannot be transferred.

[0278] Hereinafter, other Examples 1 to 4 and other Comparative Examples 1 and 2 (hereinafter, sometimes simply referred to as examples) for further specifically describing the embodiment of the present invention will be described.

[0279] A. Phase-Shift Mask Blanks and Methods of Making Them

[0280] In each of the other Examples 1 to 4 and the other Comparative Examples 1 and 2, in order to manufacture a phase shift mask blank, a synthetic quartz glass substrate of 1214 size (1220 mm×1400 mm) was first prepared as the transparent substrate 20 .

[0281] Then, in each example, the synthetic quartz glass substrate was placed on a tray (not shown) with the main surface facing downward, and was transported into the chamber of the inline sputtering apparatus.

[0282] In order to form the phase shift film 30 on the main surface of the transparent substrate 20, first, a mixed gas containing argon (Ar), helium (He) and nitrogen (N2) is introduced into the first chamber. The sputtering gas pressure during the introduction is set to different values ​​in each example by adjusting the flow rates of argon (Ar), helium (He) and nitrogen (N2) within the range where the phase shift film satisfies a given transmittance and phase difference (see Table 1 below). As shown in Table 1, the sputtering gas pressure in each of the other Examples 1 to 4 satisfies the range of 0.7 Pa or more and 2.4 Pa or less, and the sputtering gas pressure in the other Comparative Examples 1 and 2 does not satisfy the range of 0.7 Pa or more and 2.4 Pa or less. Then, in each example, a sputtering power of 7.6 kW is applied to a first sputtering target containing molybdenum and silicon (molybdenum: silicon = 1:9), and a nitride of a molybdenum silicide containing molybdenum, silicon and nitrogen is deposited on the main surface of the transparent substrate 20 by reactive sputtering, thereby forming a phase shift film 30. In each example, the film thickness of the phase shift film 30 is 144 nm to 170 nm.

[0283] Next, in each case, the transparent substrate 20 with the phase shift film 30 was transported to the second chamber, and a mixed gas of argon (Ar) and nitrogen (N2) was introduced into the second chamber. Then, a sputtering power of 1.5 kW was applied to the second sputtering target made of chromium, and chromium nitride (CrN) (film thickness 15 nm) containing chromium and nitrogen was formed on the phase shift film 30 by reactive sputtering. Next, in a state where the third chamber was made to be a given vacuum degree, a mixed gas of argon (Ar) and methane (CH4: 4.9%) was introduced, and a sputtering power of 8.5 kW was applied to the third sputtering target made of chromium, and chromium carbide (CrC) (film thickness 60 nm) containing chromium and carbon was formed on CrN by reactive sputtering. Finally, in a state where the fourth chamber is set to a given vacuum degree, a mixed gas of argon (Ar) and methane (CH4: 5.5%) and a mixed gas of nitrogen (N2) and oxygen (O2) are introduced, and a sputtering power of 2.0 kW is applied to the fourth sputtering target made of chromium, and chromium carbonitride oxide (CrCON) (film thickness 30 nm) containing chromium, carbon, oxygen and nitrogen is formed on CrC by reactive sputtering. As shown above, in each case, an etching mask film 40 having a stacked structure of a CrN layer, a CrC layer and a CrCON layer is formed on the phase shift film 30.

[0284] Thus, in each example, the phase shift mask blank 10 in which the phase shift film 30 and the etching mask film 40 were formed on the transparent substrate 20 was obtained.

[0285] In each example, the transmittance and phase difference of the phase shift film 30 (the surface of the phase shift film 30) of the obtained phase shift mask blank 10 were measured using MPM-100 manufactured by Lasertec. In the measurement of the transmittance and phase difference of the phase shift film 30, a substrate with a phase shift film (model substrate) in which the phase shift film 30 was formed on the main surface of a synthetic quartz glass substrate was used, and the substrate with a phase shift film was mounted on the same tray. In each example, the substrate with a phase shift film (model substrate) was taken out from the chamber before forming the etching mask film 40, and the transmittance and phase difference of the phase shift film 30 were measured. As a result, in each example, the transmittance and phase difference satisfied the required range (transmittance: 10 to 50% at a wavelength of 405 nm, phase difference: 160° or more and 200° or less at a wavelength of 405 nm).

[0286] In addition, in each example, the obtained phase shift mask blank 10 was subjected to composition analysis in the depth direction by X-ray photoelectron spectroscopy (XPS).

[0287] In each example, as a result of the depth-direction composition analysis of the phase shift mask blank 10 by XPS, in the phase shift film 30, the content of each constituent element in the depth direction is substantially constant except for the composition gradient region at the interface between the transparent substrate 20 and the phase shift film 30 and the composition gradient region at the interface between the phase shift film 30 and the etching mask film 40. In addition, in each example, the atomic ratio of molybdenum to silicon is within the range of 1:3 or more and 1:15 or less.

[0288] Then, in each example, the indentation hardness of the obtained phase shift film 30 was measured. Specifically, the measurement position was set at a 6×6 matrix position (36 positions) with a pitch of 50um in the phase shift film 30 in each example, and a special probe with a diamond indenter was pressed at a maximum of 0.5mN at each position to measure the change in load. The indentation hardness of each example was calculated by removing abnormal values ​​and the maximum and minimum values ​​from the measured values ​​obtained at each position (see Table 1). It should be noted that by removing abnormal values ​​and the maximum and minimum values, it was confirmed that the standard deviation relative to the measured value was less than 7% of the measured value.

[0289] As shown in Table 1, the indentation hardness of other Examples 1 to 4 satisfied 18 GPa or more and 23 GPa or less, and the indentation hardness of other Comparative Examples 1 and 2 did not satisfy 18 GPa or more and 23 GPa or less.

[0290] B. Phase-Shift Mask and Method of Making the Same

[0291] In order to manufacture the phase shift mask 100 using the phase shift mask blank 10 manufactured as described above, first, in each example, a photoresist film was applied on the etching mask film 40 of the phase shift mask blank 10 using a resist coating apparatus.

[0292] Then, through a heating / cooling process, a photoresist film with a film thickness of 520 nm was formed.

[0293] Then, the photoresist film was patterned using a laser drawing device, and after a development / rinsing process, a resist film pattern having a hole pattern with a hole diameter of 1.5 μm was formed on the etching mask film.

[0294] Then, in each example, the etching mask film was wet-etched using a chromium etching solution containing ammonium cerium nitrate and perchloric acid, using the resist film pattern as a mask, thereby forming a first etching mask film pattern 40 a .

[0295] Then, in each example, the phase shift film 30 was wet-etched using the first etching mask film pattern 40 a as a mask with a molybdenum silicide etching solution obtained by diluting a mixed solution of ammonium hydrofluoride and hydrogen peroxide with pure water, thereby forming a phase shift film pattern 30 a.

[0296] In order to make the cross-sectional shape vertical and to form a desired fine pattern, the wet etching was performed with an overetching time of 110% in each example.

[0297] The etching rates of the phase shift film 30 in each example are shown in Table 1. As shown in Table 1, the etching rate of Comparative Example 1 was the smallest at 1.0 nm / min, and the etching rate of Comparative Example 2 was the largest at 12.0 nm / min.

[0298] Then, the resist film pattern is peeled off.

[0299] Then, a photoresist film is applied using a resist coating apparatus so as to cover the first etching mask film pattern 40 a .

[0300] Then, through a heating / cooling process, a photoresist film with a film thickness of 520 nm was formed.

[0301] Then, a photoresist film is drawn using a laser drawing device, and after a development / rinsing process, a second resist film pattern 60 for forming a light shielding band is formed on the first etching mask film pattern 40a.

[0302] Then, the first etching mask film pattern 40 a formed in the transfer pattern formation region was wet-etched using the second resist film pattern 60 as a mask with a chromium etching solution containing ammonium cerium nitrate and perchloric acid.

[0303] Then, the second resist film pattern 60 is peeled off.

[0304] In addition, in each example, a cleaning process using a reagent (sulfuric acid / hydrogen peroxide water (SPM), ammonia / hydrogen peroxide water (SC1), ozone water) was appropriately performed.

[0305] Thus, in each example, a phase shift mask 100 was obtained, wherein on the transparent substrate 20, a phase shift film pattern 30a with an aperture of 1.5 μm was provided in the transfer pattern forming region, and a light shielding film consisting of a stacked structure of the phase shift film pattern 30a and the etching mask film pattern 40b was formed on the transparent substrate 20.

[0306] [Table 1]

[0307] Other Embodiment 1 Other Embodiment 2 Other Embodiment 3 Other Embodiment 4 Other Comparative Example 1 Other Comparative Example 2 Pressure [Pa] 1.6 1.9 1.1 0.7 0.5 2.5 Etching rate [nm / min] 7.4 8.6 5.8 3.3 1.0 12.0 Indentation hardness [GPa] 19.3 18.3 21.3 23.0 26.2 17.5 Rough substrate surface OK OK OK OK NG OK Washability OK OK OK OK OK NG

[0308] Table 1 shows the following results respectively: the sputtering gas pressure (Pa) during the formation of the phase shift film 30 in other embodiments 1 to 4 and other comparative examples 1 and 2, the etching rate (nm / min) of the phase shift film 30, the indentation hardness (GPa) of the phase shift film 30, the surface roughness of the transparent substrate 20 caused by wet etching, and the cleaning resistance of the phase shift film 30.

[0309] in addition, Fig.14This is a graph showing the relationship among the etching rate, sputtering gas pressure, and indentation hardness of the phase shift film 30 of the phase shift mask 100 of other Examples 1 to 4 and other Comparative Examples 1 and 2. Fig.14 From the left to the right (in order of etching rate from small to large), the indentation hardness and sputtering gas pressure of other comparative example 1, other embodiment 4, other embodiment 3, other embodiment 2, other embodiment 1, and other comparative example 2 are shown. Fig.14 As shown, a correlation is observed between the etching rate of the phase shift film 30 and the indentation hardness or the sputtering gas pressure.

[0310] The cross section of the obtained phase shift mask was observed using a scanning electron microscope. The cross section of the phase shift film pattern is composed of the upper surface, lower surface and side surface of the phase shift film pattern. The angle of the cross section of the phase shift film pattern refers to the angle formed by the portion where the upper surface of the phase shift film pattern is connected to the side surface (upper side) and the portion where the side surface is connected to the lower surface (lower side). As a result, the cross-sectional shape of the phase shift film pattern 30a of the phase shift mask of other embodiments 1 to 4 and other comparative example 2 is in the range of 65° to 75°, and all have a cross-sectional shape that can fully exert the phase shift effect. The surface of the transparent substrate 20 exposed by the phase shift mask 100 of other embodiments 1 to 4 is smooth, and the transmittance reduction caused by the rough surface of the transparent substrate 20 can be ignored. Therefore, for exposure light containing light in the wavelength range of 300nm or more and 500nm or less, more specifically, for exposure light containing composite light of i-line, h-line and g-line, a phase shift mask with excellent phase shift effect is obtained.

[0311] Therefore, when the phase shift masks of other Examples 1 to 4 are set on the mask stage of an exposure device and the resist film transferred to the display device is exposed, a fine pattern of less than 2.0 μm can be transferred with high accuracy.

[0312] It should be noted that columnar structures were observed in the phase shift film patterns 30 a of the phase shift masks 100 of other Examples 1 to 4.

[0313] In contrast, the surface of the exposed transparent substrate 20 of the phase shift mask 100 of Comparative Example 1 is rough and appears cloudy when observed with the naked eye. Therefore, the transmittance reduction caused by the rough surface of the transparent substrate 20 is significant.

[0314] Therefore, it is predicted that when the phase shift mask 100 of other comparative example 1 is set on the mask stage of an exposure device and the resist film to be transferred to the display device is exposed, a fine pattern smaller than 2.0 μm cannot be transferred.

[0315] In addition, the surface of the transparent substrate 20 exposed in the phase shift mask 100 of other comparative example 2 is smooth, and the transmittance reduction caused by the rough surface of the transparent substrate 20 is negligible. However, the amount of change in transmittance and the amount of change in phase difference caused by the reagents (sulfuric acid / hydrogen peroxide water (SPM), ammonia / hydrogen peroxide water (SC1), and ozone water) used in cleaning the phase shift mask 100 are large, and the transmittance and phase difference required by the phase shift mask 100 are not satisfied.

[0316] Therefore, it is predicted that when the phase shift mask of Comparative Example 2 is set on the mask stage of an exposure device and the resist film to be transferred to a display device is exposed, a fine pattern smaller than 2.0 μm cannot be transferred.

[0317] It should be noted that no columnar structure was observed in the phase shift film pattern 30 a of the phase shift mask 100 of Comparative Example 1. The same is true for the phase shift film pattern 30 a of the phase shift mask 100 of Comparative Example 2.

Claims

1. A photomask blank having a pattern-forming thin film on a transparent substrate, wherein: The pattern-forming thin film contains a transition metal and silicon. The pattern-forming film has a columnar structure, The columnar structure of the pattern forming film is in a state where, in an image of spatial spectrum distribution, with the center of the image of spatial spectrum distribution being the origin of the spatial spectrum, there is a spatial spectrum having a signal intensity of 1.0% or more relative to a maximum signal intensity in the image of spatial spectrum distribution corresponding to the origin of the spatial frequency in the image of spatial spectrum distribution, The spatial spectrum distribution is obtained as follows: for an image obtained by observing the cross section of the photomask blank with a scanning electron microscope at a magnification of 80,000 times, image data of 64 pixels in length by 256 pixels in width are extracted from an area including the center portion in the thickness direction of the pattern-forming film, and the image data is Fourier transformed.

2. The photomask blank according to claim 1, wherein: The columnar structure of the pattern-forming film is in the following state: in the pattern data, when the origin is set to 0% and the maximum spatial frequency corresponding to the two ends of the 256 pixels on the horizontal axis is set to 100% to set the horizontal axis, the signal with a signal strength of more than 1.0% is located at a position on the horizontal axis that is more than 2.0% away from the origin of the spatial frequency.

3. The photomask blank according to claim 1, wherein: The atomic ratio of the transition metal and the silicon contained in the pattern-forming thin film is transition metal:silicon=1:3 or more and 1:15 or less.

4. The photomask blank according to claim 1, wherein: In the columnar structure of the pattern-forming thin film, columnar particles extending in the film thickness direction are formed over the entire surface of the transparent substrate.

5. The photomask blank according to claim 4, wherein: The columnar particles are irregularly formed in a direction perpendicular to a film thickness direction of the pattern-forming thin film.

6. The photomask blank according to claim 1, wherein: The pattern-forming thin film contains at least nitrogen or oxygen.

7. The photomask blank according to claim 1, wherein: The transition metal is molybdenum.

8. The photomask blank according to claim 1, wherein: The pattern-forming thin film is a phase shift film having the following optical properties: a transmittance of a representative wavelength of exposure light of 1% to 80% and a phase difference of 160° to 200°. 9 . The photomask blank according to claim 1 , further comprising an etching mask film having a different etching selectivity with respect to the pattern forming thin film on the pattern forming thin film.

10. The photomask blank according to claim 9, wherein: The etching mask film is formed of a material containing chromium but substantially containing no silicon.

11. A method for manufacturing a photomask, the method comprising: A step of preparing the photomask blank according to any one of claims 1 to 8; and A step of forming a resist film on the pattern-forming thin film, and wet-etching the pattern-forming thin film using a resist film pattern formed by the resist film as a mask to form a transfer pattern on the transparent substrate.

12. A method for manufacturing a photomask, the method comprising: A step of preparing the photomask blank according to claim 9 or 10; forming a resist film on the etching mask film, and wet-etching the etching mask film using the resist film pattern formed by the resist film as a mask to form an etching mask film pattern on the pattern-forming thin film; and A step of wet-etching the pattern-forming thin film using the etching mask film pattern as a mask to form a transfer pattern on the transparent substrate.

13. A method for manufacturing a display device, the method comprising: An exposure step of placing the photomask obtained by the photomask manufacturing method according to claim 11 or 12 on a mask stage of an exposure device, and transferring the transfer pattern formed on the photomask to a resist formed on a display device substrate by exposure.